Steel plate, member and manufacturing method thereof

A steel plate with a controlled microstructure and processing achieves high tensile strength and formability, addressing the limitations of existing steel plates in impact energy absorption and axial crush tests, particularly for automobile frame members.

JP7601257B2Active Publication Date: 2024-12-17JFE STEEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023565497
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-11
Filing Date
2023-02-27
Publication Date
2024-12-17
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

Current steel plates with a tensile strength exceeding 590 MPa used in automobile frame members face challenges in achieving high impact energy absorption due to reduced press formability, particularly in properties such as ductility, hole expandability, and bendability, leading to inadequate performance in axial crush tests.

Method used

A steel plate composition with controlled microstructure ratios of ferrite, bainite, tempered bainite, and tempered martensite, along with specified elements and processing conditions, ensuring a tensile strength of 1180 MPa or more, high yield stress and yield ratio, and excellent press formability, bendability, and fracture resistance.

Benefits of technology

The steel plate achieves high tensile strength, yield stress, and yield ratio, along with improved press formability, hole expandability, and bendability, enhancing its performance in impact energy absorption and axial crush properties, making it suitable for automobile frame members.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601257000013
    Figure 0007601257000013
  • Figure 0007601257000014
    Figure 0007601257000014
  • Figure 0007601257000015
    Figure 0007601257000015
Patent Text Reader

Abstract

The purpose of the present invention is to achieve a TS of at least 1180 MPa, high YS and YR, excellent press formability (ductility, hole expandability, and bendability), and rupture resistance at impact (flexural rupture properties and axial crush properties). A base steel plate is made to have a predetermined chemical composition. In a steel microstructure at 1 / 4 of the thickness of the base steel plate, the amounts of ferrite, fresh martensite, retained austenite, bainite, tempered bainite, and tempered martensite are within predetermined ranges, the average grain size of island-like fresh martensite and island-like retained austenite in bainite grains and tempered bainite grains is 2.00 μm or less, the average grain size of carbides in the bainite grains and the tempered bainite grains is 500 nm or less, and the number density of carbides having a grain size of at least 300 nm in the bainite grains and the tempered bainite grains is 3.0 / μm2 or less. The amount of diffusible hydrogen contained in the base steel plate is 0.50 ppm by mass or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel plate, a member made of the steel plate, and a method for producing the same. [Background technology]

[0002] In order to achieve both reduction in CO2 emissions by improving fuel efficiency through the reduction in thickness and weight of steel sheets used in automobile bodies and improvement in collision safety, efforts are being made to increase the strength of steel sheets for automobiles. In addition, new laws and regulations are being introduced one after another. For this reason, in order to increase the strength of automobile bodies, the application of high-strength steel sheets, particularly high-strength steel sheets with a tensile strength (hereinafter also simply referred to as TS) of 780 MPa or more, to major structural members and reinforcing members (hereinafter also referred to as automobile skeleton structural members, etc.) to be assembled to the skeleton of an automobile cabin is increasing. In addition, high-strength steel sheets used in automobile skeleton structural members, etc. are required to have high member strength when press-formed. For example, it is effective to increase the strength of parts by increasing the yield ratio (hereinafter also simply referred to as YR), which is the value obtained by dividing the yield stress (hereinafter also simply referred to as YS) of a steel sheet by TS. This increases the impact absorption energy (hereinafter also simply referred to as impact absorption energy) during an automobile collision. Furthermore, among the automobile skeleton structural members, for example, crash boxes have bending parts. Therefore, from the viewpoint of press formability, it is preferable to apply a steel sheet having high bendability to such parts. Also, from the viewpoint of the rust prevention performance of the vehicle body, the steel sheet used as the material of the automobile parts is often zinc-plated. Therefore, there is a demand for the development of a hot-dip galvanized steel sheet having excellent press formability and impact resistance in addition to having high strength.

[0003] As an example of a steel sheet that can be used as a material for such automobile components, Patent Document 1 discloses a high-strength steel sheet that has a component composition that contains, expressed by mass%, 0.04 to 0.22% C, 1.0% or less Si, 3.0% or less Mn, 0.05% or less P, 0.01% or less S, 0.01 to 0.1% Al, and 0.001 to 0.005% N, with the balance being Fe and unavoidable impurities, and that is composed of a ferrite phase as a main phase and a martensite phase as a second phase, and that has a maximum grain size of 2 μm or less and an area ratio of the martensite phase of 5% or more, and has excellent stretch flangeability and crash resistance.

[0004] In addition, Patent Document 2 discloses a method for forming a 0.2 g / m2 Ni alloy on a cold-rolled steel sheet from which a surface layer of 0.1 μm or more has been removed by grinding. 2 More than 2.0g / m 2The following hot-dip galvanized steel sheet has a hot-dip galvanized layer on the surface of a pre-galvanized cold rolled steel sheet, and contains, by mass%, C: 0.05% or more and 0.4% or less, Si: 0.01% or more and 3.0% or less, Mn: 0.1% or more and 3.0% or less, P: 0.04% or less, S: 0.05% or less, N: 0.01% or less, Al: 0.01% or more and 2.0% or less, Si + Al > 0.5%, the balance being Fe and unavoidable impurities, and the microstructure contains, by volume fraction, 40% or more of ferrite as a main phase, 8% or more of retained austenite, two or more of three types of martensite [1] [2] [3] specified below including martensite [3], 1% or more of bainite, and 0 to 10% of pearlite, and further contains the three types of martensite [1] [2] [3] as specified below. A high-strength hot-dip galvanized steel sheet having excellent coating adhesion and formability, characterized in that the steel sheet has a surface in which the sites [1], [2] and [3] are, in volume fraction, martensite [1]: 0% or more and 50% or less, martensite [2]: 0% or more and less than 20%, and martensite [3]: 1% or more and 30% or less, respectively, and has a hot-dip galvanized layer containing less than 7% Fe and the balance consisting of Zn, Al and unavoidable impurities, and has a tensile strength TS (MPa), total elongation EL (%) and hole expansion ratio λ (%) of TS×EL of 18000 MPa·% or more and TS×λ of 35000 MPa·% or more, and a tensile strength of 980 MPa or more (martensite [1]: C concentration (CM1) is less than 0.8%, and hardness Hv1 is Hv1 / (-982.1×CM1 2 +1676×CM1+189)≦0.60, martensite [2]: C concentration (CM2) is 0.8% or more, and hardness Hv2 is Hv2 / (-982.1×CM2 2 +1676×CM2+189)≦0.60, martensite [3]: C concentration (CM3) is 0.8% or more, and hardness Hv3 is Hv3 / (-982.1×CM3 2 +1676×CM3+189)≧0.80 is disclosed.

[0005] Patent Document 3 discloses a high-strength hot-dip galvanized steel sheet having a component composition, in mass%, of C: 0.15% or more and 0.25% or less, Si: 0.50% or more and 2.5% or less, Mn: 2.3% or more and 4.0% or less, P: 0.100% or less, S: 0.02% or less, Al: 0.01% or more and 2.5% or less, with the balance being Fe and unavoidable impurities, and having, in area ratios, a tempered martensite phase: 30% or more and 73% or less, a ferrite phase: 25% or more and 68% or less, a retained austenite phase: 2% or more and 20% or less, and other phases: 10% or less (including 0%), and the other phases include a martensite phase: 3% or less (including 0%) and a bainitic ferrite phase: less than 5% (including 0%), the tempered martensite phase has an average crystal grain size of 8 μm or less, and the retained austenite phase has a C content of less than 0.7% by mass.

[0006] Patent Document 4 also describes a galvannealed steel sheet having a galvannealed layer on the surface of the steel sheet, the steel sheet having a chemical composition, in mass%, of C: 0.03% to 0.35%, Si: 0.005% to 2.0%, Mn: 1.0% to 4.0%, P: 0.0004% to 0.1%, S: 0.02%, sol.Al: 0.0002% to 2.0%, N: 0.01%, the balance being Fe and impurities, and an average spacing of enriched portions, which is an average spacing in the direction perpendicular to the rolling direction of enriched portions in which Mn and / or Si are enriched and which extend in the rolling direction at a position 50 μm deep from the surface of the steel sheet, is 1 The steel sheet has a steel structure in which the surface area of ​​the steel sheet is 0.000 μm or less, the number density of cracks having a depth of 3 μm or more and 10 μm or less on the surface of the steel sheet is 3 / mm or more and 1000 / mm or less, the steel sheet contains, in area percentages, 60% or more bainite, 1% or more retained austenite, 1% or more martensite, and 2% or more and less than 20% ferrite, and the average spacing of ultra-hard phases, which is the average value of the closest distances of martensite and retained austenite, is 20 μm or less, and the galvannealed steel sheet has mechanical properties such as a tensile strength (TS) of 780 MPa or more. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 3887235 [Patent Document 2] Patent No. 5953693 [Patent Document 3] Patent No. 6052472 [Patent Document 4] Patent No. 5699764 Summary of the Invention [Problem to be solved by the invention]

[0008] Incidentally, the use of steel plates with a tensile strength TS (hereinafter sometimes simply referred to as TS) exceeding 590 MPa is becoming more common in automobile frame components such as center pillars, but the current situation is that the use of steel plates with a TS of 590 MPa or less is limited to automobile impact energy absorbing components such as front side members and rear side members.

[0009] That is, in order to increase the energy absorbed during a collision (hereinafter also referred to as the impact absorption energy), it is effective to improve the yield stress YS (hereinafter sometimes simply referred to as YS) and the yield ratio YR (hereinafter sometimes simply referred to as YR). However, when the YS and YR of a steel plate are increased, generally, the press formability, particularly properties such as ductility, hole expandability, and bendability, are reduced. Therefore, when it is assumed that such a steel plate with increased TS and YS is applied to the impact energy absorption member of an automobile, not only does press forming become difficult, but the member is cracked in an axial crushing test simulating a crash test, in other words, the actual impact absorption energy is not as high as expected from the value of YS. Therefore, the current situation is that the impact energy absorption member is limited to the application of a steel plate with a TS of 590 MPa.

[0010] In fact, the steel plates disclosed in Patent Documents 1 to 4 have a TS of 1180 MPa or more, and cannot be said to have high YS and YR, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance during collision (flexural fracture properties and axial crush properties).

[0011] The present invention has been developed in view of the above-mentioned current situation, and aims to provide a steel plate having a tensile strength TS of 1180 MPa or more, as well as high yield stress YS and high yield ratio YR, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance properties during collision (flexural fracture properties and axial crush properties), and a manufacturing method thereof. Another object of the present invention is to provide a member made of the above-mentioned steel plate and a method for manufacturing the same.

[0012] The steel sheet referred to here also includes a zinc-plated steel sheet, and the zinc-plated steel sheet is a hot-dip galvanized steel sheet (hereinafter also referred to as GI) or an alloyed hot-dip galvanized steel sheet (hereinafter also referred to as GA).

[0013] Here, the tensile strength TS is measured by a tensile test in accordance with JIS Z 2241 (2011). In addition, high yield stress YS and yield ratio YR refer to that YS measured in a tensile test conforming to JIS Z 2241 (2011) satisfies the following formula (A) or (B) depending on TS measured in the tensile test. (A) When 1180MPa≦TS<1320MPa, 750MPa≦YS and 0.64≦YR (B) When TS is 1320MPa or less, YS is 850MPa or less and YR is 0.64 or less.

[0014] In addition, excellent ductility means that the total elongation (El) measured in a tensile test conforming to JIS Z 2241 (2011) satisfies the following formula (A) or (B) depending on the TS measured in the tensile test. (A) When 1180MPa≦TS<1320MPa, 8.0%≦El (B) 1320MPa≦TS, 7.0%≦El

[0015] In addition, excellent hole expansion property means that the limit hole expansion ratio (λ) measured in a hole expansion test conforming to JIS Z 2256 (2020) is 25% or more.

[0016] In addition, excellent bendability means that R (limit bending radius) / t (plate thickness) measured in a V-bend test conforming to JIS Z 2248 (2014) satisfies the following formula (A) or (B) depending on TS. (A) When 1180MPa≦TS<1320MPa, 2.5≧R / t (B) When TS is 1320MPa or less, R / t is 3.0 or more

[0017] In addition, excellent axial crushing properties means that the limit spacer thickness (ST) in a U-bend + close contact bending test satisfies the following formula (A) or (B) depending on TS. (A) When 1180MPa≦TS<1320MPa, 5.5mm≧ST (B) When TS is 1320MPa or less, ST is 6.0mm or more

[0018] Furthermore, excellent axial crushing properties means that the stroke at maximum load (SFmax) measured in a V-bend + orthogonal VDA bending test satisfies the following formula (A) or (B) depending on TS. (A) When 1180MPa≦TS<1320MPa, 25.5mm≦SFmax (B) When TS is 1320MPa or less, SFmax is 24.5mm or less

[0019] Furthermore, excellent axial crushing properties means that after an axial crushing test, there is one or less fracture (visual crack) within a range of R = 5.0 mm, 200 mm of the two lower bend ridge lines in Figure 4(b) (see area Cx in Figures 4(a) and (b)).

[0020] In addition, excellent bending fracture properties means that the limit spacer thickness (ST) in the above U-bend + close-contact bending test satisfies the above formula (A) or (B) depending on TS, and the stroke at maximum load (SFmax) measured in the V-bend + orthogonal VDA bending test satisfies the above formula (A) or (B) depending on TS.

[0021] The above El (ductility), λ (stretch flangeability), and R / t (bendability) are properties that indicate the ease of forming a steel sheet during press forming (the degree of freedom in forming to press form without cracking). On the other hand, the U-bend + close bending test is a test that simulates the deformation and fracture behavior of the vertical wall in a crash test, and the critical spacer thickness (ST) measured in the U-bend + close bending test is an index that indicates the resistance of the steel sheet and components of an automobile body to cracking during a crash (the impact resistance properties to absorb impact energy without breaking). In addition, the V-bend + orthogonal VDA bend test is a test that simulates the deformation and fracture behavior of the bend ridge during a crash test, and the stroke at maximum load (SFmax) measured in the V-bend + orthogonal VDA bend test is an index that indicates the resistance of the energy absorbing material to cracking. [Means for solving the problem]

[0022] Means for Solving the Problems The present inventors have conducted extensive research to achieve the above object, and as a result have obtained the following findings. (1) With the specified composition, a TS of 1,180 MPa or more can be ensured by controlling the area fraction of ferrite to less than 20.0%, the area fraction of bainite and tempered bainite to more than 10.0%, and the area fraction of tempered martensite to 30.0% or more. (2) With a specified composition, high YS and YR can be ensured by controlling the area fraction of ferrite to less than 20.0%, the area fraction of bainite and tempered bainite to more than 10.0%, and the area fraction of tempered martensite to 30.0% or more. (3) By controlling the area fraction of bainite and tempered bainite to more than 10.0% with a specified composition, it is possible to improve El, which is an index of ductility that correlates with stretch formability, which is one mode of press formability. (4) With a specified composition, the area ratio of fresh martensite is controlled to 15.0% or less, the area ratio of retained austenite is controlled to 3.0% or less, the average crystal grain size of isolated island-like hard second phases (martensite + retained austenite) in bainite grains and tempered bainite grains is controlled to 2.00 μm or less, and further, the number density of carbides with a grain size of 300 nm or more in bainite grains and tempered bainite grains is controlled to 3.0 pieces / μm 2 By setting the following, it is possible to realize an improvement in λ, which is an index of hole expandability correlated with stretch flangeability, which is one mode of press formability. (5) With a specified composition, the area ratio of fresh martensite is controlled to 15.0% or less, the average crystal grain size of isolated island martensite in bainite grains and tempered bainite grains is controlled to 2.00 μm or less, and the number density of carbides with a grain size of 300 nm or more in bainite grains and tempered bainite grains is controlled to 3.0 pieces / μm 2 By setting the ratio to the above range, it is possible to improve R / t, which is an index of bendability, which is one mode of press formability. (6) With Si: 0.75 mass% or less and a specified composition, the area ratio of retained austenite is controlled to 3.0% or less, which makes it possible to suppress the formation of hard fresh martensite formed by the processing-induced transformation of retained austenite that occurs during primary processing such as punching and press forming, and to suppress the formation of voids and the propagation of cracks in subsequent tests. Furthermore, by controlling the area ratio of fresh martensite to 15.0% or less, making the average crystal grain size of the isolated island-like hard second phase (martensite + retained austenite) within the bainite grains and tempered bainite grains 2.00 μm or less, and further making the number density of carbides with a grain size of 300 nm or more within the bainite grains and tempered bainite grains 3.0 / μm 2 By satisfying the following, it is possible to improve the limit spacer thickness (ST) measured in a U-bend + close-contact bend test, which simulates the deformation and fracture behavior of the vertical wall in a crash test, and the stroke at maximum load (SFmax) measured in a V-bend + orthogonal VDA bend test, which simulates the deformation and fracture behavior of the bent ridge in a crash test, which are indicators of the impact resistance properties of steel plates and components of an automobile body during a crash.

[0023] The present disclosure has been made based on the above findings. That is, the gist of the present disclosure is as follows. [1] A steel plate having a base steel plate, the base steel plate comprising: In mass%, C: 0.030% or more and 0.250% or less, Si: 0.01% or more and 0.75% or less, Mn: 2.00% or more and less than 3.50% P: 0.001% or more and 0.100% or less, S: 0.0200% or less, Al: 0.010% or more and 2.000% or less, N: 0.0100% or less, and the balance being Fe and unavoidable impurities; The structure at 1 / 4 of the thickness of the base steel sheet is as follows: Ferrite area ratio: less than 20.0% Area ratio of fresh martensite: 15.0% or less, Area ratio of retained austenite: 3.0% or less; Area ratio of bainite and tempered bainite: more than 10.0% and not more than 70.0%; Area ratio of tempered martensite: 30.0% or more and 80.0% or less; Furthermore, the average grain size of the fresh martensite islands and the retained austenite islands within the bainite grains and the tempered bainite grains is 2.00 μm or less, The average grain size of carbides in bainite grains and tempered bainite grains is 500 nm or less; Furthermore, the number density of carbides with a grain size of 300 nm or more in the bainite grains and tempered bainite grains is 3.0 / μm 2 A steel structure having the following structure: having The base steel sheet has a diffusible hydrogen content of 0.50 mass ppm or less and a tensile strength of 1180 MPa or more. [2] The composition further includes, in mass%, Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co:0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less and REM: 0.0200% or less The steel sheet according to the above [1], containing at least one element selected from the following: [3] The steel sheet according to [1] or [2] above, which has a zinc-plated layer as the outermost layer on one or both sides of the steel sheet. [4] When the base steel sheet has a surface layer of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction, The surface layer has a soft surface layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 points or more in a 50 μm × 50 μm region of the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, The ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet to the total number of measurements at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer is 0.10 or less, Furthermore, the standard deviation σ of the nanohardness of the sheet surface at a position of 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, The steel sheet according to any one of the above [1] to [3], wherein the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less. [5] The steel sheet according to any one of [1] to [4] above, which has a metal plating layer formed on the base steel sheet on one or both sides of the steel sheet. [6] A member made using the steel plate according to any one of [1] to [5] above. [7] A steel slab having the composition described in [1] or [2] above, A hot rolling process in which hot rolling is performed under a finish rolling temperature of 820°C or higher to obtain a hot-rolled steel sheet; An annealing process in which the steel sheet after the hot rolling process is annealed under the conditions of an annealing temperature of (Ac1+(Ac3-Ac1)×5 / 8)°C or more and 950°C or less and an annealing time of 20 seconds or more; After the annealing step, a first cooling step is performed to cool the steel sheet to a temperature range of 300°C or more and 550°C or less. After the first cooling step, an intermediate holding step is performed under the conditions of an intermediate holding temperature of 300° C. or more and 550° C. or less and a holding time of 20 seconds or more. After the intermediate holding process, the steel plate is subjected to a tensile strength of 2.0 kgf / mm in the temperature range of 300°C to 450°C. 2 Applying a tension of more than Thereafter, the steel sheet is passed through five or more passes while being in contact with a roll having a diameter of 500 mm or more and 1500 mm or less for one pass for 1 / 4 of the circumference of the roll, Then, a second cooling step of cooling to a cooling stop temperature of less than 300°C; a reheating step of reheating the steel sheet to a temperature range of the cooling stop temperature or higher and 440°C or lower after the second cooling step, and holding the temperature for 20 seconds or more, or The method for producing a steel sheet includes a cold rolling step of cold rolling the steel sheet after the hot rolling step and before the annealing step at a rolling reduction rate of 20% or more and 80% or less to obtain a cold-rolled steel sheet. [8] The method for producing a steel sheet according to [7], further comprising a galvanizing step of subjecting the steel sheet after the intermediate holding step and before the second cooling step to a galvanizing treatment to form a galvanized layer on the steel sheet. [9] The method for producing a zinc-plated steel sheet according to [7] or [8], wherein the annealing in the annealing step is carried out in an atmosphere with a dew point of -30°C or higher.

[10] The method for producing a steel sheet according to any one of [7] to [9] above, further comprising a metal plating step of applying metal plating to one or both sides of the steel sheet to form a metal plating layer after the hot rolling step and before the annealing step.

[11] A method for producing a component, comprising the step of subjecting the steel plate according to any one of [1] to [5] above to at least one of forming and joining to produce a component. Effect of the Invention

[0024] According to the present invention, a steel plate can be obtained which has a tensile strength TS of 1180 MPa or more, high yield stress YS and yield ratio YR, excellent press formability (ductility, hole expandability and bendability), and fracture resistance during collision (bending fracture properties and axial crush properties). Furthermore, members made from the steel plate of the present invention have high strength, excellent press formability and impact resistance, and can therefore be extremely advantageously used for automobile frame members and impact energy absorbing members, etc. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is an example of an SEM image of the present invention (Example No. 13 of the present invention). [Diagram 2]Fig. 2(a) is a diagram for explaining the U-bending (primary bending) in the U-bending + contact bending test of the embodiment, and Fig. 2(b) is a diagram for explaining the contact bending (secondary bending) in the U-bending + contact bending test of the embodiment. [Diagram 3] Fig. 3(a) is a diagram for explaining the V-bending (primary bending) in the V-bending + orthogonal VDA bending test of the embodiment, and Fig. 3(b) is a diagram for explaining the orthogonal VDA bending (secondary bending) in the V-bending + orthogonal VDA bending test of the embodiment. [Figure 4] Fig. 4(a) is a front view of a test member produced for the axial crush test of the embodiment, in which a hat-shaped member and a steel plate are spot-welded together. Fig. 4(b) is a perspective view of the test member shown in Fig. 4(a). Fig. 4(c) is a schematic diagram for explaining the axial crush test of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present invention will be described based on the following embodiments.

[0027] [1. Steel plate] The steel sheet of the present invention is a steel sheet having a base steel sheet, the base steel sheet containing, by mass%, C: 0.030% or more and 0.250% or less, Si: 0.01% or more and 0.75% or less, Mn: 2.00% or more and less than 3.50%, P: 0.001% or more and 0.100% or less, S: 0.0200% or less, Al: 0.010% or more and 2.000% or less, N: 0.0100% or less, with the balance being Fe and unavoidable impurities, and the structure at the 1 / 4 position of the sheet thickness of the base steel sheet has an area ratio of ferrite: less than 20.0%, an area ratio of fresh martensite: 15.0% or less, and retained austenite: area ratio of austenite: 3.0% or less, area ratio of bainite and tempered bainite: more than 10.0% and not more than 70.0%, area ratio of tempered martensite: 30.0% or more and not more than 80.0%, further, the average crystal grain size of island-shaped fresh martensite and island-shaped retained austenite within the bainite grains and tempered bainite grains is 2.00 μm or less, the average crystal grain size of carbides within the bainite grains and tempered bainite grains is 500 nm or less, and the number density of carbides with a grain size of 300 nm or more within the bainite grains and tempered bainite grains is 3.0 pieces / μm 2 or less, the amount of diffusible hydrogen contained in the base steel sheet is 0.50 ppm by mass or less, and the tensile strength is 1180 MPa or more. The steel sheet may have a zinc plating layer as the outermost layer on one or both sides of the steel sheet. The steel sheet having a zinc plating layer may be a zinc-plated steel sheet.

[0028] Ingredient composition First, the composition of the base steel sheet of the steel sheet according to the embodiment of the present invention will be described. Note that the unit of the composition is always "mass%", but hereinafter, unless otherwise specified, it will be simply shown as "%".

[0029] C: 0.030% or more and 0.250% or less C is an effective element for ensuring a TS of 1180 MPa or more, high YS and high YR by generating an appropriate amount of tempered martensite, bainite, and tempered bainite. Here, if the C content is less than 0.030%, the area ratio of ferrite increases, making it difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS and YR. On the other hand, when the C content exceeds 0.250%, the area ratio of fresh martensite increases, TS becomes excessively high, and El decreases. In addition, the area ratio of fresh martensite increases, the bendability in the V-bend test decreases, and the desired R / t (press formability) cannot be obtained. Furthermore, the area ratio of retained austenite increases, and when the steel plate is subjected to punching in the hole expansion test, U-bending in the U-bend + close bending test, or V-bending in the V-bend + orthogonal VDA test, hard fresh martensite is generated by the processing-induced transformation of retained austenite, and voids are generated and cracks grow in the subsequent tests, and the desired λ (press formability), ST (fracture resistance at the time of collision) and SFmax (fracture resistance at the time of collision) cannot be obtained. Therefore, the C content is 0.030% or more and 0.250% or less. The C content is preferably 0.080% or more. In addition, the C content is preferably 0.160% or less.

[0030] Si: 0.01% or more and 0.75% or less Silicon promotes ferrite transformation during annealing and in the cooling process after annealing. That is, silicon is an element that affects the area ratio of ferrite. If the silicon content is less than 0.01%, the area ratio of ferrite decreases, and ductility decreases. On the other hand, if the Si content exceeds 0.75%, the volume fraction of the retained austenite increases, and when the steel sheet is subjected to punching in the hole expansion test, U-bending in the U-bending + close bending test, or V-bending in the V-bending + orthogonal VDA test, hard fresh martensite is generated due to the deformation-induced transformation of the retained austenite, and voids are generated and cracks grow in the subsequent tests, so that the desired λ, ST, and SFmax cannot be obtained. Therefore, the Si content is set to 0.01% or more and 0.75% or less. The Si content is preferably 0.10% or more. The Si content is also preferably 0.70% or less.

[0031] Mn: 2.00% or more and less than 3.50% Mn is an element that adjusts the area ratio of tempered martensite, bainite, and further tempered bainite. If the Mn content is less than 2.00%, the area ratio of ferrite increases, making it difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS and YR. On the other hand, if the Mn content is 3.50% or more, the martensite transformation start temperature Ms (hereinafter also simply referred to as Ms point or Ms) decreases, and the martensite generated in the first cooling step decreases. As a result, the fresh martensite generated in the second cooling step increases, and the fresh martensite is not sufficiently tempered in the subsequent reheating step, the area ratio of the fresh martensite increases, the bendability in the V-bend test decreases, and the desired R / t cannot be obtained. Therefore, the Mn content is set to 2.00% or more and less than 3.50%. The Mn content is preferably 2.30% or more. Moreover, the Mn content is preferably 3.30% or less.

[0032] P: 0.001% or more and 0.100% or less P is an element that has a solid solution strengthening effect and increases the TS and YS of a steel sheet. To obtain this effect, the P content is set to 0.001% or more. On the other hand, if the P content exceeds 0.100%, P segregates at the prior austenite grain boundaries and embrittles the grain boundaries. Therefore, during the V-bend test, voids are generated and cracks grow along the prior austenite grain boundaries, and the desired R / t cannot be obtained. In addition, when the steel sheet is subjected to punching in the hole expansion test, U-bending in the U-bend + close bending test, or V-bending in the V-bend + orthogonal VDA test, voids are generated and cracks grow along the prior austenite grain boundaries, and the desired λ, ST, and SFmax cannot be obtained. Therefore, the P content is 0.001% or more and 0.100% or less. The P content is preferably 0.030% or less.

[0033] S: 0.0200% or less S exists as sulfides in steel. In particular, if the S content exceeds 0.0200%, voids are generated and cracks grow from the sulfides during a V-bend test, and the desired R / t cannot be obtained. In addition, when the steel plate is subjected to punching in a hole expansion test, U-bending in a U-bend + close bending test, or V-bending in a V-bend + orthogonal VDA test, voids are generated and cracks grow from the sulfides, and the desired λ, ST, and SFmax cannot be obtained. Therefore, the S content is set to 0.0200% or less. The S content is preferably 0.0080% or less. Although there is no particular lower limit for the S content, due to constraints on production technology, the S content is preferably 0.0001% or more.

[0034] Al: 0.010% or more and 2.000% or less Al promotes ferrite transformation during annealing and in the cooling process after annealing. That is, Al is an element that affects the area ratio of ferrite. Here, if the Al content is less than 0.010%, the area ratio of ferrite decreases, and ductility decreases. On the other hand, if the Al content exceeds 2.000%, the area ratio of ferrite increases excessively, making it difficult to achieve a TS of 1180 MPa or more. This also leads to a decrease in YS and YR. Therefore, the Al content is set to 0.010% or more and 2.000% or less. The Al content is preferably 0.015% or more. Moreover, the Al content is preferably 1.000% or less.

[0035] N: 0.0100% or less N exists as nitrides in steel. In particular, if the N content exceeds 0.0100%, voids are generated and cracks grow from the nitrides during a V-bend test, and the desired R / t cannot be obtained. In addition, when the steel sheet is subjected to punching in a hole expansion test, U-bending in a U-bend + close bending test, or V-bending in a V-bend + orthogonal VDA test, voids are generated and cracks grow from the nitrides, and the desired λ, ST, and SFmax cannot be obtained. Therefore, the N content is set to 0.0100% or less. In addition, the N content is preferably 0.0050% or less. Although there is no particular lower limit for the N content, due to constraints on production technology, the N content is preferably 0.0005% or more.

[0036] The basic composition of the base steel sheet of the steel sheet according to one embodiment of the present invention has been described above, but the base steel sheet of the steel sheet according to one embodiment of the present invention has a composition containing the above basic components with the balance other than the above basic components including Fe (iron) and unavoidable impurities. Here, it is preferable that the base steel sheet of the steel sheet according to one embodiment of the present invention has a composition containing the above basic components with the balance consisting of Fe and unavoidable impurities.

[0037] In addition to the basic components described above, the base steel sheet of the steel sheet according to one embodiment of the present invention may contain at least one selected from the optional components shown below. The effects of the present invention can be obtained so long as the optional components shown below are contained in amounts not exceeding the upper limit amounts shown below, so no lower limit is set. When the optional elements shown below are contained in amounts less than the preferred lower limit values ​​described below, the elements are considered to be included as unavoidable impurities.

[0038] Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0. 200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200 %, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less, and at least one selected from REM: 0.0200% or less.

[0039] Nb: 0.200% or less Nb forms fine carbides, nitrides, or carbonitrides during hot rolling or annealing, thereby increasing TS, YS, and YR. To obtain such effects, the Nb content is preferably 0.001% or more. The Nb content is more preferably 0.005% or more. On the other hand, if the Nb content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of voids and cracks during the hole expansion test, V-bend test, U-bend + close bending test, or V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Nb is contained, the Nb content is preferably 0.200% or less. The Nb content is more preferably 0.060% or less.

[0040] Ti:0.200% or less Ti, like Nb, forms fine carbides, nitrides, or carbonitrides during hot rolling or annealing, thereby increasing TS, YS, and YR. To obtain such an effect, the Ti content is preferably 0.001% or more. The Ti content is more preferably 0.005% or more. On the other hand, if the Ti content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of voids and cracks during the hole expansion test, V-bend test, U-bend + close bending test, or V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Ti is contained, the Ti content is preferably 0.200% or less. The Ti content is more preferably 0.060% or less.

[0041] V:0.200% or less Like Nb and Ti, V forms fine carbides, nitrides, or carbonitrides during hot rolling or annealing, thereby increasing TS and YS. To obtain such an effect, the V content is preferably 0.001% or more. The V content is more preferably 0.005% or more. The V content is further preferably 0.010% or more, and even more preferably 0.030% or more. On the other hand, if the V content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of voids and cracks during a hole expansion test, a V-bend test, a U-bend + close contact bending test, or a V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when V is contained, the V content is preferably 0.200% or less. The V content is more preferably 0.060% or less.

[0042] B: 0.0100% or less B is an element that enhances hardenability by segregating at the austenite grain boundaries. Also, B is an element that controls the formation and grain growth of ferrite during cooling after annealing. To obtain such effects, the B content is preferably 0.0001% or more. The B content is more preferably 0.0002% or more. The B content is more preferably 0.0005% or more, and even more preferably 0.0007% or more. On the other hand, if the B content exceeds 0.0100%, cracks may occur inside the steel sheet during hot rolling. In addition, the internal cracks become the starting points of cracks during a hole expansion test, a V-bend test, a U-bend + close contact bending test, or a V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when B is contained, the B content is preferably 0.0100% or less. The B content is more preferably 0.0050% or less.

[0043] Cr:1.000% or less Cr is an element that enhances hardenability, and the addition of Cr produces an appropriate amount of tempered martensite, thereby increasing TS, YS, and YR. To obtain such effects, the Cr content is preferably 0.0005% or more. The Cr content is more preferably 0.010% or more. The Cr content is more preferably 0.030% or more, and even more preferably 0.050% or more. On the other hand, if the Cr content exceeds 1.000%, the area ratio of fresh martensite increases, the hole expandability and the bendability in the V-bend test decrease, and the desired λ and R / t may not be obtained. Therefore, when Cr is contained, the Cr content is preferably 1.000% or less. The Cr content is more preferably 0.800% or less, and further preferably 0.700% or less.

[0044] Ni: 1.000% or less Ni is an element that enhances hardenability, and the addition of Ni produces a large amount of tempered martensite, thereby increasing TS, YS, and YR. To obtain such an effect, the Ni content is preferably 0.005% or more. The Ni content is more preferably 0.020% or more. The Ni content is further preferably 0.040% or more, and even more preferably 0.060% or more. On the other hand, if the Ni content exceeds 1.000%, the area ratio of fresh martensite increases, the hole expandability and the bendability in the V-bend test decrease, and the desired λ and R / t may not be obtained. Therefore, when Ni is contained, the Ni content is preferably 1.000% or less. The Ni content is more preferably 0.800% or less. The Ni content is more preferably 0.600% or less, and even more preferably 0.400% or less.

[0045] Mo: 1.000% or less Mo is an element that enhances hardenability, and the addition of Mo produces a large amount of tempered martensite, thereby increasing TS, YS, and YR. To obtain such effects, the Mo content is preferably 0.010% or more. The Mo content is more preferably 0.030% or more. On the other hand, if the Mo content exceeds 1.000%, the area ratio of fresh martensite increases, the hole expandability and the bendability in the V-bend test decrease, and the desired λ and R / t may not be obtained. Therefore, when Mo is contained, the Mo content is preferably 1.000% or less. The Mo content is more preferably 0.500% or less, further preferably 0.450% or less, and even more preferably 0.400% or less. The Mo content is more preferably 0.350% or less, and even more preferably 0.300% or less.

[0046] Sb: 0.200% or less Sb is an element that is effective in suppressing the diffusion of C near the steel sheet surface during annealing and controlling the formation of a soft layer near the steel sheet surface. If the soft layer increases excessively near the steel sheet surface, it may be difficult to achieve a TS of 1180 MPa or more. In addition, it may lead to a decrease in YS. Therefore, the Sb content is preferably 0.002% or more. The Sb content is more preferably 0.005% or more. On the other hand, if the Sb content exceeds 0.200%, a soft layer is not formed near the steel sheet surface, which may result in a decrease in λ, R / t, ST, and SFmax. Therefore, when Sb is contained, the Sb content is preferably 0.200% or less. The Sb content is more preferably 0.020% or less.

[0047] Sn: 0.200% or less Like Sb, Sn is an element that is effective in suppressing the diffusion of C near the steel sheet surface during annealing and controlling the formation of a soft layer near the steel sheet surface. If the soft layer increases excessively near the steel sheet surface, it may be difficult to achieve a TS of 1180 MPa or more. In addition, it may lead to a decrease in YS. Therefore, the Sn content is preferably 0.002% or more. The Sn content is more preferably 0.005% or more. On the other hand, if the Sn content exceeds 0.200%, a soft layer is not formed near the steel sheet surface, which may result in a decrease in λ, R / t, ST, and SFmax. Therefore, when Sn is contained, the Sn content is preferably 0.200% or less. The Sn content is more preferably 0.020% or less.

[0048] Cu:1.000% or less Cu is an element that enhances hardenability, and the addition of Cu produces a large amount of tempered martensite, thereby increasing TS, YS, and YR. To obtain such an effect, the Cu content is preferably 0.005% or more. The Cu content is more preferably 0.008% or more, and even more preferably 0.010% or more. The Cu content is more preferably 0.020% or more. On the other hand, if the Cu content exceeds 1.000%, the area ratio of fresh martensite may increase excessively. Also, a large amount of coarse precipitates and inclusions may be generated. In such a case, the excessively generated fresh martensite and the coarse precipitates and inclusions may become the starting points of voids and cracks during the hole expansion test, V-bend test, U-bend + close bending test, or V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Cu is contained, the Cu content is preferably 1.000% or less. The Cu content is more preferably 0.200% or less.

[0049] Ta:0.100% or less Ta, like Ti, Nb and V, increases TS, YS and YR by forming fine carbides, nitrides or carbonitrides during hot rolling or annealing. In addition, Ta partially dissolves in Nb carbides or Nb carbonitrides to generate composite precipitates such as (Nb,Ta)(C,N). This inhibits the coarsening of precipitates and stabilizes precipitation strengthening. This further improves TS and YS. To obtain such effects, the Ta content is preferably 0.001% or more. The Ta content is more preferably 0.002% or more, and even more preferably 0.004% or more. On the other hand, if the Ta content exceeds 0.100%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the excessively coarse precipitates and inclusions may become the starting points of voids and cracks during a hole expansion test, a V-bend test, a U-bend + close contact bending test, or a V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Ta is contained, the Ta content is preferably 0.100% or less. The Ta content is more preferably 0.090% or less, and even more preferably 0.080% or less.

[0050] W: 0.500% or less W is an element that enhances hardenability, and the addition of W produces a large amount of tempered martensite, thereby increasing TS, YS, and YR. To obtain such effects, the W content is preferably 0.001% or more. The W content is more preferably 0.030% or more. On the other hand, if the W content exceeds 0.500%, the area ratio of fresh martensite increases, the hole expandability and the bendability in the V-bend test decrease, and the desired λ and R / t may not be obtained. Therefore, when W is contained, the W content is preferably 0.500% or less. The W content is more preferably 0.450% or less, and even more preferably 0.400% or less. The W content is even more preferably 0.300% or less.

[0051] Mg: 0.0200% or less Mg is an element that is effective in making the shape of inclusions such as sulfides and oxides spherical and improving the hole expandability and bendability of steel sheets. To obtain such effects, the Mg content is preferably 0.0001% or more. The Mg content is more preferably 0.0005% or more, and even more preferably 0.0010% or more. On the other hand, if the Mg content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the excessively coarse precipitates and inclusions may become the starting points of voids and cracks during a hole expansion test, a V-bend test, a U-bend + close contact bending test, or a V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Mg is contained, the Mg content is preferably 0.0200% or less. The Mg content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0052] Zn: 0.0200% or less Zn is an element that is effective in making the shape of inclusions spherical and improving the hole expandability and bendability of the steel sheet. To obtain such effects, the Zn content is preferably 0.0010% or more. The Zn content is more preferably 0.0020% or more, and even more preferably 0.0030% or more. On the other hand, if the Zn content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the excessively coarse precipitates and inclusions may become the starting points of voids and cracks during a hole expansion test, a V-bend test, a U-bend + close contact bending test, or a V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Zn is contained, the Zn content is preferably 0.0200% or less. The Zn content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0053] Co:0.0200% or less Like Zn, Co is an element that is effective in making the shape of inclusions spherical and improving the hole expandability and bendability of the steel sheet. To obtain such effects, the Co content is preferably 0.0010% or more. The Co content is more preferably 0.0020% or more, and even more preferably 0.0030% or more. On the other hand, if the Co content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the excessively coarse precipitates and inclusions may become the starting points of voids and cracks during a hole expansion test, a V-bend test, a U-bend + close contact bending test, or a V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Co is contained, the Co content is preferably 0.0200% or less. The Co content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0054] Zr: 0.1000% or less Like Zn and Co, Zr is an effective element for spheroidizing the shape of inclusions and improving the hole expandability and bendability of steel sheets. In order to obtain such effects, the Zr content is preferably 0.0010% or more. On the other hand, if the Zr content exceeds 0.1000%, in such cases, excessively coarse precipitates and inclusions may become the starting points of voids and cracks during hole expansion tests, V-bending tests, U-bending + close bending tests, or V-bending + orthogonal VDA bending tests, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Zr is contained, the Zr content is preferably 0.1000% or less. The Zr content is more preferably 0.0300% or less, and further preferably 0.0100% or less.

[0055] Ca:0.0200% or less Ca exists as inclusions in steel. Here, if the Ca content exceeds 0.0200%, a large amount of coarse inclusions may be generated. In such a case, the excessively coarse precipitates and inclusions may become the starting points of voids and cracks during a hole expansion test, a V-bend test, a U-bend + close contact bending test, or a V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST, and SFmax may not be obtained. Therefore, when Ca is contained, the Ca content is preferably 0.0200% or less. The Ca content is preferably 0.0020% or less. The Ca content is more preferably 0.0019% or less, and even more preferably 0.0018% or less. The lower limit of the Ca content is not particularly limited, but the Ca content is preferably 0.0005% or more. In addition, due to constraints on production technology, the Ca content is more preferably 0.0010% or more.

[0056] Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less and REM: 0.0200% or less Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are all elements effective for improving the hole expandability and bendability of steel sheet. In order to obtain such effects, the contents of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are each preferably 0.0001% or more. On the other hand, when the contents of Se, Te, Ge, Sr, Cs, Hf, Pb, Bi and REM exceed 0.0200%, or when the content of As exceeds 0.0500%, coarse precipitates and inclusions may be generated in large quantities. In such cases, the excessively coarse precipitates and inclusions may become the starting points of voids and cracks during the hole expansion test, V-bend test, U-bend + close contact bending test and V-bend + orthogonal VDA bending test, so that the desired λ, R / t, ST and SFmax may not be obtained. Therefore, when at least one of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM is contained, it is preferable that the contents of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are each 0.0200% or less, and the As content is 0.0500% or less. The Se content is more preferably 0.0005% or more, and further preferably 0.0008% or more.The Se content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Te content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Te content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The Ge content is more preferably 0.0005% or more, and further preferably 0.0008% or more.The Ge content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The As content is more preferably 0.0010% or more, and further preferably 0.0015% or more.The As content is more preferably 0.0400% or less, and further preferably 0.0300% or less. The Sr content is more preferably 0.0005% or more, and further preferably 0.0008% or more.The Sr content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Cs content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Cs content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The Hf content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Hf content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The Pb content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Pb content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The Bi content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Bi content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The REM content is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The REM content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. In the present invention, REM refers to scandium (Sc), which has atomic number 21, yttrium (Y), which has atomic number 39, and the lanthanoids ranging from lanthanum (La), which has atomic number 57, to lutetium (Lu), which has atomic number 71. The REM concentration in the present invention refers to the total content of one or more elements selected from the above-mentioned REMs. The REM is not particularly limited, but is preferably Sc, Y, Ce, or La.

[0057] steel structure Next, the steel structure of the base steel sheet of the steel sheet according to one embodiment of the present invention will be described.

[0058] Ferrite area ratio: Less than 20.0% (including 0.0%) If the area ratio of ferrite is excessively increased, it becomes difficult to achieve TS of 1180 MPa or more. In addition, it also leads to a decrease in YS and YR. Therefore, the area ratio of ferrite is less than 20.0% (including 0.0%). In addition, the area ratio of ferrite is preferably 15.0% or less.

[0059] Area ratio of fresh martensite: 15.0% or less (including 0.0%) In the present invention, if the area ratio of fresh martensite is excessively increased, the fresh martensite becomes the starting point of void generation during the hole expanding process in the hole expanding test or during the bending process in the V-bending test, and the desired λ and R / t cannot be obtained. Therefore, the area ratio of fresh martensite is set to 15.0% or less. In addition, the area ratio of fresh martensite is preferably 10.0% or less. The lower limit of the area ratio of fresh martensite is not particularly limited and may be 0.0%. The fresh martensite referred to here is martensite as quenched (not tempered). The fresh martensite referred to here also includes (isolated) island-like fresh martensite within bainite grains and tempered bainite grains, which will be described later.

[0060] Area ratio of retained austenite: 3.0% or less (including 0.0%) In the present invention, if the area ratio of the retained austenite is excessively increased, when the steel plate is subjected to punching in the hole expansion test, U-bending in the U-bending + close bending test, or V-bending in the V-bending + orthogonal VDA test, hard fresh martensite is generated by the deformation-induced transformation of the retained austenite, and voids are generated and cracks grow in the subsequent tests, making it impossible to obtain the desired λ, ST, and SFmax. Therefore, the area ratio of the retained austenite is set to 3.0% or less. The area ratio of the retained austenite is preferably 2.5% or less, more preferably 2.0% or less. The lower limit of the area ratio of the retained austenite is not particularly limited, but is preferably 0.1% or more, and more preferably 0.2% or more. The retained austenite referred to here also includes (isolated) island-like retained austenite within bainite grains and tempered bainite grains, which will be described later.

[0061] Here, during the second cooling step in the manufacturing method described later, the temperature range is 300°C to 450°C, and the compression strength is 2.0 kgf / mm 2 The above tension is applied to the steel sheet, and then the steel sheet is passed through 5 or more passes while being in contact with rolls having a diameter of 500 mm or more and 1500 mm or less for 1 / 4 of the circumference of the roll per pass, whereby untransformed austenite undergoes processing-induced transformation to become fresh martensite, and the fresh martensite is tempered in the subsequent reheating process. By controlling the area ratio of fresh martensite to be 15.0% or less and the area ratio of retained austenite to be 3.0% or less, it is possible to ensure the desired area ratio of tempered martensite.

[0062] Area ratio of bainite and tempered bainite: over 10.0% and up to 70.0% Bainite (B) is a structure formed in the first cooling step and the intermediate holding step, as shown in Fig. 1. Moreover, tempered bainite (BT) referred to here is a structure in which the bainite formed in the reheating step is tempered, as shown in Fig. 1. In Fig. 1, F: ferrite, M: martensite, RA: retained austenite, TM: tempered martensite, and θ: carbide. When the area fraction of bainite and tempered bainite is 10.0% or less, it becomes difficult to ensure good ductility, that is, to obtain a desired El, so the area fraction of bainite and tempered bainite is set to more than 10.0%. On the other hand, if the area fraction of bainite and tempered bainite is excessively increased beyond 70.0%, it becomes difficult to ensure a TS of 1180 MPa or more. Therefore, the area fraction of bainite and tempered bainite is set to 70.0% or less. Moreover, the area fraction of bainite and tempered bainite is preferably 15.0% or more. Moreover, the area fraction of bainite and tempered bainite is preferably 65.0% or less.

[0063] Area ratio of tempered martensite: 30.0% to 80.0% Tempered martensite is a structure obtained in the reheating process. Here, the hard second phase (fresh martensite + retained austenite) is an effective structure for ensuring the desired TS, but since it is a structure that promotes the generation of voids and the propagation of cracks during press forming and collision, the area ratio of fresh martensite must be 15.0% or less and the volume ratio of retained austenite must be 3.0% or less. In particular, during the second cooling process in the manufacturing method described below, a pressure of 2.0 kgf / mm2 must be maintained in the temperature range of 300°C to 450°C. 2 The above tension is applied, and then the steel sheet is passed through five or more passes while being in contact with rolls having a diameter of 500 mm to 1500 mm per pass for 1 / 4 rotation of the roll, whereby the untransformed austenite undergoes a deformation-induced transformation to become fresh martensite, and the fresh martensite is tempered in the subsequent reheating process to become tempered martensite. That is, the tempered martensite is a structure necessary to obtain the desired λ, R / t, ST, and SFmax. Therefore, the area ratio of the tempered martensite is set to 30.0% or more. The area ratio of the tempered martensite is preferably 35.0% or more. On the other hand, if the area ratio of tempered martensite is excessively increased, the desired area ratio of bainite and tempered bainite cannot be obtained, and it becomes difficult to ensure good ductility, that is, to obtain the desired El. Therefore, the area ratio of tempered martensite is set to 70.0% or less. The area ratio of tempered martensite is preferably 60.0% or less.

[0064] Average grain size of fresh martensite islands and retained austenite islands within bainite grains and tempered bainite grains: 2.00μm or less In the present invention, when the average grain size of the isolated fresh martensite islands and the isolated retained austenite islands in the bainite grains and the tempered bainite grains is small, the generation of voids can be suppressed more while ensuring a TS of 1180 MPa or more, and better λ, R / t, ST and SFmax can be obtained. Therefore, the average grain size of the isolated fresh martensite islands and the isolated retained austenite islands in the bainite grains and the tempered bainite grains is set to 2.00 μm or less. In the present invention, the average grain size of the isolated fresh martensite islands and the isolated retained austenite islands in the bainite grains and the tempered bainite grains can be the average grain size of the fresh martensite islands and the retained austenite islands in the bainite grains and the tempered bainite grains. That is, in the present invention, the average grain size of the fresh martensite islands and the retained austenite islands in the bainite grains and the tempered bainite grains is set to 2.00 μm or less. The average grain size of the island-like fresh martensite and island-like retained austenite in the bainite grains and tempered bainite grains is preferably 1.00 μm or less. Although there is no particular lower limit, the average crystal grain size of the island-like fresh martensite and island-like retained austenite in the bainite grains and tempered bainite grains is preferably 0.10 μm or more, and more preferably 0.20 μm or more.

[0065] Average grain size of carbides in bainite grains and tempered bainite grains: 500 nm or less In the present invention, when the average grain size of the carbides in the bainite grains and the tempered bainite grains is small, the generation of voids can be suppressed while ensuring a TS of 1180 MPa or more, and better λ, R / t, ST and SFmax can be obtained. Therefore, the average grain size of the carbides in the bainite grains and the tempered bainite grains is set to 500 nm or less. The average grain size of the carbides in the bainite grains and the tempered bainite grains is preferably 300 nm or less. Although there is no particular lower limit, the average crystal grain size of carbides in bainite grains and tempered bainite grains is preferably 50 nm or more, and more preferably 80 nm or more.

[0066] Number density of carbides with a grain size of 300 nm or more in bainite grains and tempered bainite grains: 3.0 pieces / μm 2 below In the present invention, when the number density of carbides with a grain size of 300 nm or more in the bainite grains and tempered bainite grains is small, the generation of voids can be suppressed while ensuring a TS of 1180 MPa or more, and better λ, R / t, ST and SFmax can be obtained. Therefore, the number density of carbides with a grain size of 300 nm or more in the bainite grains and tempered bainite grains is 3.0 particles / μm 2 The number density of carbides with a grain size of 300 nm or more in bainite grains and tempered bainite grains is preferably 2.5 / μm 2 The following is the result. Although there is no particular lower limit, the number density of carbides in bainite grains and tempered bainite grains is preferably 0.2 particles / μm 2 More preferably, it is 0.5 particles / μm or more. 2 That's all.

[0067] The area ratio of the remaining structure other than the above-mentioned ferrite, fresh martensite, retained austenite, bainite, tempered bainite, and tempered martensite is preferably 10.0% or less. The area ratio of the remaining structure is more preferably 5.0% or less. Moreover, the area ratio of the remaining structure may be 0.0%.

[0068] The remaining structure is not particularly limited, and examples thereof include unrecrystallized ferrite, pearlite, etc. The type of the remaining structure can be confirmed, for example, by observation with a SEM (Scanning Electron Microscope).

[0069] Here, the area ratios of ferrite, bainite, tempered bainite, tempered martensite and hard second phase (fresh martensite + retained austenite) are measured at a 1 / 4 position in the sheet thickness of the base steel sheet as follows. That is, a sample is cut out so that the plate thickness cross section (L cross section) parallel to the rolling direction of the steel plate becomes the observation surface. Next, the observation surface of the sample is polished with diamond paste, and then finish polished with alumina. Next, the observation surface of the sample is etched with 3 vol.% nital to reveal the structure. Next, the observation position is set to 1 / 4 of the plate thickness of the steel plate, and five fields of view are observed at a magnification of 3000 times using an SEM. From the obtained structure image, the area ratio of each constituent structure (ferrite, bainite, tempered bainite, tempered martensite, and hard second phase (fresh martensite + retained austenite)) is calculated by dividing the area by the measured area for the five fields of view using Adobe Photoshop by Adobe Systems, and these values ​​are averaged to obtain the area ratio of each structure. Ferrite: A black region that is lumpy in shape. It contains almost no carbides. Also, isolated islands of fresh martensite and isolated islands of retained austenite within the ferrite grains are not included in the area ratio of ferrite. Bainite and tempered bainite: These are areas that are black to dark gray in color and have blocky or amorphous morphology. They also contain a relatively small number of carbides. Tempered martensite: This is a gray area with an amorphous shape. It also contains a relatively large number of carbides. Hard second phase (retained austenite + fresh martensite): This is a region that is white to light gray in color and has an amorphous morphology. It also does not contain carbides. Carbides: These are white areas that are dotted or linear in shape. They are included in bainite, tempered bainite, and tempered martensite. Remaining structure: The above-mentioned unrecrystallized ferrite and pearlite are included, and the morphology thereof is as known.

[0070] From the SEM images used in the above structure fraction measurements, isolated fresh martensite islands and isolated retained austenite islands within bainite grains and tempered bainite grains are manually extracted, and the average grain sizes of the isolated fresh martensite islands and isolated retained austenite islands within bainite grains and tempered bainite grains are calculated using the open source ImageJ. The average grain size is calculated by dividing the total area of ​​the island-shaped fresh martensite and the island-shaped retained austenite by the number of island-shaped fresh martensite and island-shaped retained austenite to obtain an average area, dividing the average area by pi, and multiplying the square root of the result by 2 to obtain a circle-equivalent diameter, which is the average grain size. With regard to an isolated island of fresh martensite or an isolated island of retained austenite, an island region in an SEM image that is surrounded by bainite and / or tempered bainite and formed without interruption is counted as one island. In addition, only the carbides within the bainite grains and tempered bainite grains are manually extracted from the SEM images used in the above-mentioned structure fraction measurements, and the average crystal grain size of the carbides within the bainite grains and tempered bainite grains, as well as the number density of carbides with a grain size of 300 nm or more among the carbides within the bainite grains and tempered bainite grains, are determined using the open source ImageJ. The average crystal grain size is determined by dividing the total area of ​​the carbides by the number of carbides to obtain an average area, dividing the average area by pi, and multiplying the square root of the result by 2 to obtain a circle-equivalent diameter. With regard to one carbide, an island-like region that is surrounded by bainite and / or tempered bainite on the outer periphery in the SEM image and is formed integrally without interruption is counted as one carbide when measuring.

[0071] The area ratio of retained austenite is measured as follows. That is, the base steel plate is mechanically ground in the plate thickness direction (depth direction) to a position of 1 / 4 of the plate thickness, and then chemically polished with oxalic acid to obtain the observation surface. The observation surface is then observed by X-ray diffraction. MoKα rays are used as the incident X-rays, and the ratio of the diffraction intensity of the (200), (211), and (220) faces of the fcc iron (austenite) to the diffraction intensity of the (200), (220), and (311) faces of the bcc iron is calculated, and the volume fraction of the retained austenite is calculated from the ratio of the diffraction intensity of each face. The retained austenite is then considered to be three-dimensionally homogeneous, and the volume fraction of the retained austenite is taken as the area fraction of the retained austenite.

[0072] The area ratio of fresh martensite is determined by subtracting the area ratio of retained austenite from the area ratio of the hard second phase determined as described above. [Area ratio of fresh martensite (%)] = [Area ratio of hard second phase (%)] - [Area ratio of retained austenite (%)]

[0073] The area fraction of the remaining structure is determined by subtracting the area fraction of ferrite, the area fraction of bainite and tempered bainite, the area fraction of tempered martensite, and the area fraction of the hard second phase determined as described above from 100.0%. [Area ratio of remaining structure (%)] = 100.0 - [Area ratio of ferrite (%)] - [Area ratio of bainite and tempered bainite (%)] - [Area ratio of tempered martensite (%)] - [Area ratio of hard second phase (%)]

[0074] Amount of diffusible hydrogen contained in the base steel sheet (in steel): 0.50 mass ppm or less If the amount of diffusible hydrogen in the steel sheet exceeds 0.50 ppm by mass, the desired λ, R / t, ST and SFmax cannot be obtained. The amount of diffusible hydrogen in the steel sheet is preferably 0.25 ppm by mass or less. Although there is no particular lower limit for the amount of diffusible hydrogen in the steel sheet, due to constraints on production technology, the amount of diffusible hydrogen in the steel sheet is preferably 0.01 ppm by mass or more. The base steel sheet for measuring the amount of diffusible hydrogen may be a high-strength steel sheet before plating, a base steel sheet of a high-strength galvanized steel sheet after galvanization but before processing, a base steel sheet of a steel sheet that has been subjected to processing such as punching and stretch flange forming after galvanization, or a base part of a product manufactured by welding processed steel sheets.

[0075] Here, the method for measuring the amount of diffusible hydrogen in a steel sheet is as follows. A test piece having a length of 30 mm and a width of 5 mm is taken, and in the case where a zinc-plated layer is formed on the steel sheet, the hot-dip galvanized layer or the alloyed hot-dip galvanized layer is removed by alkali. Then, the amount of hydrogen released from the test piece is measured by thermal desorption analysis. Specifically, the test piece is continuously heated from room temperature (-5 to 55°C) to 300°C at a heating rate of 200°C / h, and then cooled to room temperature, and the cumulative amount of hydrogen released from the test piece from room temperature to 210°C is measured and defined as the amount of diffusible hydrogen in the steel sheet. The measurement of the amount of diffusible hydrogen is preferably performed after the completion of the production of the steel sheet. It is more preferable to measure the amount of hydrogen within one week after the completion of the production of the steel sheet. In addition, taking into consideration production in various countries around the world, the room temperature should be within the range of local temperature changes over the course of a year. In general, a range of 10 to 50°C is preferable.

[0076] surface soft layer In the base steel sheet of the steel sheet according to one embodiment of the present invention, it is preferable that the base steel sheet has a soft surface layer on its surface. The soft surface layer contributes to suppressing bending crack propagation during press forming and vehicle body collision, thereby further improving bending fracture resistance. The soft surface layer means a decarburized layer, and is a surface region having a Vickers hardness of 85% or less of the Vickers hardness of the cross section at 1 / 4 of the plate thickness. Here, the soft surface layer is formed in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction. The region in which the soft surface layer is formed is preferably 150 μm or less, more preferably 120 μm or less, from the surface of the base steel sheet in the sheet thickness direction. There is no particular lower limit for the thickness of the soft surface layer, but it is preferably 7 μm or more, and more preferably more than 14 μm. The soft surface layer is preferably 30 μm or more, more preferably 40 μm or more. The 1 / 4 sheet thickness position of the base steel sheet where the Vickers hardness is measured is a non-surface soft layer (a layer that does not satisfy the hardness conditions of the surface soft layer defined in the present invention). Vickers hardness is measured based on JIS Z 2244-1 (2020) at a load of 10 gf.

[0077] Nano-hardness of the soft surface layer When the nano hardness is measured at 300 or more points in a 50 μm × 50 μm area on the sheet surface at 1 / 4 of the sheet thickness depth and 1 / 2 of the sheet thickness depth from the surface of the base steel sheet, the ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at 1 / 4 of the sheet thickness depth of the soft surface layer from the surface of the base steel sheet to the total number of measurements at 1 / 4 of the sheet thickness depth of the soft surface layer is 0.10 or less. In the present invention, in order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, when the nanohardness is measured at 300 or more points in a 50 μm×50 μm region on the sheet surface at 1 / 4 and 1 / 2 positions of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, the ratio of the number of measurements of nanohardness of 7.0 GPa or more on the sheet surface at 1 / 4 positions of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is preferably 0.10 or less to the total number of measurements at 1 / 4 positions of the sheet thickness direction depth of the soft surface layer. When the ratio of nanohardness of 7.0 GPa or more is 0.10 or less, it means that the ratio of hard structures (martensite, etc.), inclusions, etc. is small, and it is possible to further suppress the generation and connection of voids and crack growth during press forming and collision of hard structures (martensite, etc.), inclusions, etc., and to obtain excellent R / t and SFmax.

[0078] The standard deviation σ of the nano hardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nano hardness of the sheet surface at 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less. In the present invention, in order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, it is preferable that the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less. When the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less, it means that the difference in microscopic hardness is small, and it is possible to further suppress the generation and connection of voids during press forming and collision, and further the growth of cracks, and excellent R / t and SFmax are obtained. Furthermore, the preferred range of the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is preferably 1.7 GPa or less. The standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is more preferably 1.3 GPa or less. Although there is no particular lower limit, the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet may be 0.5 GPa or more. A more preferred range of the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.1 GPa or less. The standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is more preferably 1.7 GPa or less. Although there is no particular lower limit, the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet may be 0.6 GPa or more.

[0079] Here, the nano-hardness of the plate surface at the 1 / 4 and 1 / 2 positions in the plate thickness direction depth is a hardness measured by the following method. First, when a plating layer is formed, after peeling off the plating layer, mechanical polishing is performed from the surface of the base steel sheet to a position 1 / 4 of the depth in the sheet thickness direction of the soft surface layer -5 μm, buffing is performed with diamond and alumina from the surface of the base steel sheet to a position 1 / 4 of the depth in the sheet thickness direction of the soft surface layer, and colloidal silica polishing is further performed. Here, the plating layer to be peeled off is the zinc plating layer if a zinc plating layer is formed, the metal plating layer if a metal plating layer is formed, and the zinc plating layer and the metal plating layer if both a zinc plating layer and a metal plating layer are formed. Using Hysitron's tribo-950, the nano hardness is measured with a Berkovich-shaped diamond indenter under the following conditions: load: 500 μN, measurement area: 50 μm × 50 μm, and impact spacing: 2 μm. In addition, the surface soft layer is mechanically polished up to 1 / 2 the depth in the plate thickness direction, buffed with diamond and alumina, and then polished with colloidal silica.Then, using a Hysitron tribo-950, the nano hardness is measured with a Berkovich-shaped diamond indenter under the following conditions: load: 500μN, measurement area: 50μm×50μm, and impact spacing: 2μm. Nano hardness is measured at 300 or more points at a position 1 / 4 of the way through the plate thickness, and also at 300 or more points at a position 1 / 2 of the way through the plate thickness. For example, if the thickness of the surface soft layer is 100 μm, the 1 / 4 position is 25 μm from the surface of the surface soft layer, and the 1 / 2 position is 50 μm from the surface of the surface soft layer. At this 25 μm position, nano hardness is measured at 300 or more points, and also at the 50 μm position, nano hardness is measured at 300 or more points.

[0080] Metal plating layer (first plating layer) Furthermore, the steel sheet according to one embodiment of the present invention preferably has a metal plating layer (first plating layer, pre-plating layer) (note that the metal plating layer (first plating layer) excludes a galvanized layer such as a hot-dip galvanized layer or a galvannealed hot-dip galvanized layer) on one or both surfaces of the base steel sheet. The metal plating layer is preferably a metal electroplated layer, and the following description will be given taking a metal electroplated layer as an example. By forming a metal electroplating layer on the surface of the steel sheet, the outermost metal electroplating layer contributes to suppressing the occurrence of bending cracks during press forming and vehicle collisions, thereby further improving bending fracture resistance. In the present invention, the thickness of the soft layer can be increased and the axial collapse characteristics can be made very excellent by setting the dew point to above -20°C. In this regard, in the present invention, by having a metal plating layer, even if the dew point is -20°C or lower and the soft layer thickness is small, the axial collapse characteristics can be obtained that are equivalent to those in the case of a thick soft layer.

[0081] Metal species of the metal electroplating layer include Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Pt The metal may be any of Au, Hg, Ti, Pb, and Bi, but Fe is more preferable. In the following, an Fe-based electroplating layer will be described as an example, but the following conditions for Fe can be similarly adopted for other metals.

[0082] The adhesion weight of the Fe-based electroplating layer is 0g / m 2 More than 2.0 g / m 2 The upper limit of the coating weight of the Fe-based electroplating layer per side is not particularly limited, but from the viewpoint of cost, the coating weight of the Fe-based electroplating layer per side is set to 60 g / m or more. 2 The coating weight of the Fe-based electroplating layer is preferably 50 g / m 2 More preferably, it is 40 g / m or less. 2 More preferably, it is 30 g / m or less. 2 The following applies.

[0083] The adhesion weight of the Fe-based electroplating layer is measured as follows. A 10 x 15 mm sample is taken from the Fe-based electroplated steel sheet and embedded in resin to create a cross-section embedded sample. Three random locations on the cross-section are observed using a scanning electron microscope (SEM) at an accelerating voltage of 15 kV and a magnification of 2000 to 10000 times depending on the thickness of the Fe-based plating layer, and the average thickness of the three fields of view is multiplied by the specific gravity of iron to convert it into the adhesion weight of the Fe-based electroplating layer per side.

[0084] As the Fe-based electroplating layer, in addition to pure Fe, alloy plating layers such as Fe-B alloy, Fe-C alloy, Fe-P alloy, Fe-N alloy, Fe-O alloy, Fe-Ni alloy, Fe-Mn alloy, Fe-Mo alloy, Fe-W alloy, etc. can be used. The composition of the Fe-based electroplating layer is not particularly limited, but it is preferable that the composition contains one or more elements selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V and Co in a total of 10 mass% or less, with the balance being Fe and unavoidable impurities. By making the amount of elements other than Fe 10 mass% or less in total, it is possible to prevent a decrease in electrolysis efficiency and form the Fe-based electroplating layer at low cost. In the case of an Fe-C alloy, the content of C is preferably 0.08 mass% or less.

[0085] Next, the mechanical properties of the steel plate according to one embodiment of the present invention will be described.

[0086] Tensile strength (TS): 1180MPa or more The tensile strength of the steel plate according to one embodiment of the present invention is 1180 MPa or more. The standard values ​​of the yield stress (YS), yield ratio (YR), total elongation (El), limit hole expansion ratio (λ), limit spacer thickness (ST) in the U-bend + contact bending test, and stroke at maximum load (SFmax) in the V-bend + orthogonal VDA bending test, as well as the presence or absence of fracture (visual cracks) in the axial crush test, of the steel plate according to one embodiment of the present invention are as described above.

[0087] In addition, the tensile strength (TS), yield stress (YS), yield ratio (YR) and total elongation (El) are measured by a tensile test conforming to JIS Z 2241 (2011) described later in the examples. The limit hole expansion ratio (λ) is measured by a hole expansion test conforming to JIS Z 2256 (2020) described later in the examples. The limit spacer thickness (ST) is measured by a U-bend + close-fitting bend test described later in the examples. The stroke (SFmax) at maximum load in the V-bend + orthogonal VDA bend test is measured by a V-bend + orthogonal VDA bend test described later in the examples. The presence or absence of fracture (appearance crack) in the axial crush test is measured by an axial crush test described later in the examples.

[0088] Zinc plating layer (second plating layer) The steel sheet according to one embodiment of the present invention may have a zinc plating layer formed on the base steel sheet as the outermost layer (on the surface of the base steel sheet or on the surface of the metal plating layer if a metal plating layer is formed), and this zinc plating layer may be provided on only one surface of the base steel sheet, or on both surfaces. The steel sheet having a zinc plating layer may be referred to as a zinc-plated steel sheet. That is, the steel sheet of the present invention may have a base steel sheet on which a second plating layer (zinc plating layer, aluminum plating layer, etc.) is formed, or may have a base steel sheet on which a metal plating layer (first plating layer (excluding the second plating layer of the zinc plating layer)) and a second plating layer (zinc plating layer, aluminum plating layer, etc.) are formed in that order on the base steel sheet.

[0089] The galvanized layer referred to here refers to a plating layer containing Zn as a main component (Zn content of 50.0% or more), and examples thereof include a hot-dip galvanized layer and an alloyed hot-dip galvanized layer.

[0090] Here, the hot-dip galvanized layer is preferably composed of, for example, Zn, 20.0 mass% or less of Fe, and 0.001 mass% to 1.0 mass% or less of Al. The hot-dip galvanized layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0.0 mass% to 3.5 mass%. The Fe content of the hot-dip galvanized layer is more preferably less than 7.0 mass%. The remainder other than the above elements is unavoidable impurities.

[0091] In addition, the galvannealed layer is preferably composed of, for example, Zn, 20.0 mass% or less of Fe, and 0.001 mass% or more and 1.0 mass% or less of Al. In addition, the galvannealed layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0.0 mass% or more and 3.5 mass% or less. The Fe content of the galvannealed layer is more preferably 7.0 mass% or more, and more preferably 8.0 mass% or more. The Fe content of the galvannealed layer is more preferably 15.0 mass% or less, and more preferably 12.0 mass% or less. The remainder other than the above elements is unavoidable impurities.

[0092] In addition, the coating weight of the zinc-plated layer on one side is not particularly limited, but is preferably 20 g / m 2 The coating weight of the zinc-plated layer on one side is preferably 80 g / m or more. 2 It is preferable that:

[0093] The plating weight of the zinc plating layer is measured as follows. That is, a treatment solution is prepared by adding 0.6 g of a corrosion inhibitor for Fe (Ivit 700BK (registered trademark) manufactured by Asahi Chemical Industry Co., Ltd.) to 1 L of a 10 mass % aqueous hydrochloric acid solution. Next, a steel sheet to be used as a test material is immersed in the treatment solution to dissolve the zinc plating layer. The amount of mass loss of the test material before and after dissolution is then measured, and this value is divided by the surface area of ​​the base steel sheet (the surface area of ​​the part that was covered with plating) to obtain the plating coverage (g / m 2 ) is calculated.

[0094] The thickness of the steel plate according to one embodiment of the present invention is not particularly limited, but is preferably 0.5 mm or more. The plate thickness is more preferably greater than 0.8 mm. The plate thickness is further preferably 0.9 mm or more. The plate thickness is more preferably 1.0 mm or more. The plate thickness is further preferably 1.2 mm or more. The thickness of the steel plate is preferably 3.5 mm or less, and more preferably 2.3 mm or less. The width of the steel plate of the present invention is not particularly limited, but is preferably 500 mm or more, more preferably 750 mm or more, and is preferably 1600 mm or less, more preferably 1450 mm or less.

[0095] [2. Steel plate manufacturing method] Next, a method for manufacturing a steel sheet according to one embodiment of the present invention will be described. The method for producing a steel sheet of the present invention includes a hot rolling process in which a steel slab having the above-mentioned composition is hot rolled under a finish rolling temperature of 820°C or more to obtain a hot rolled steel sheet, an annealing process in which the steel sheet after the hot rolling process is annealed under conditions of an annealing temperature of (Ac1+(Ac3-Ac1)×5 / 8)°C or more and 950°C or less and an annealing time of 20 seconds or more, an annealing process in which the steel sheet after the annealing process is cooled to a temperature range of 300°C or more and 550°C or less, a first cooling process in which the steel sheet after the first cooling process is held under conditions of an intermediate holding temperature of 300°C or more and 550°C or less and a holding time of 20 seconds or more, and an intermediate holding process in which the steel sheet after the intermediate holding process is held under conditions of an intermediate holding temperature of 300°C or more and 550°C or less and a holding time of 20 seconds or more, and a pressure of 2.0 kgf / mm 2a second cooling step in which the steel sheet is cooled from room temperature to a cooling stop temperature less than 300°C after the second cooling step, and then reheated to a temperature range of the cooling stop temperature or more and 440°C or less, and held for 20 seconds or more; or a cold rolling step in which the steel sheet after the hot rolling step and before the annealing step is subjected to cold rolling with a reduction rate of 20% or more and 80% or less to obtain a cold-rolled steel sheet.

[0096] In the present invention, the method of smelting the steel material (steel slab) is not particularly limited, and any of the known smelting methods such as converters and electric furnaces are suitable. In addition, the steel slab is preferably produced by a continuous casting method in order to prevent macrosegregation, but it can also be produced by an ingot casting method, thin slab casting method, etc. In addition to the conventional method in which the steel slab is once cooled to room temperature after production and then heated again, energy-saving processes such as direct rolling and direct rolling in which the steel slab is charged into a heating furnace as a hot slab without being cooled to room temperature, or is immediately rolled after a short period of heat retention, can also be applied without any problems.

[0097] (Hot rolling process) When the slab is heated, the slab heating temperature is preferably 1100° C. or higher from the viewpoint of dissolving carbides and reducing the rolling load. In addition, the slab heating temperature is preferably 1300° C. or lower to prevent an increase in scale loss. The slab heating temperature is the temperature of the slab surface. The slab is made into a sheet bar by rough rolling under normal conditions, but when the heating temperature is low, it is preferable to heat the sheet bar using a bar heater or the like before finish rolling in order to prevent problems during hot rolling.

[0098] Finish rolling temperature: 820℃ or higher Finish rolling increases the rolling load and the reduction ratio in the unrecrystallized state of austenite, leading to the development of abnormal structures elongated in the rolling direction, which reduces the ductility, hole expandability, and bendability of the final material. For this reason, the finish rolling temperature is set to 820°C or higher. The finish rolling temperature is preferably 830°C or higher, and more preferably 850°C or higher. In addition, the finish rolling temperature is preferably 1080°C or lower, and more preferably 1050°C or lower.

[0099] The coiling temperature after hot rolling is not particularly limited, but it is necessary to consider the possibility of lowering the ductility, hole expandability, and bendability of the final material. For this reason, the coiling temperature after hot rolling is preferably 300°C or higher. The coiling temperature after hot rolling is preferably 700°C or lower.

[0100] In addition, the rough rolled sheets may be joined together during hot rolling and continuously finished rolling may be performed. The rough rolled sheets may be wound once. In order to reduce the rolling load during hot rolling, a part or all of the finish rolling may be lubricated rolling. Lubricated rolling is effective from the viewpoint of uniforming the shape of the steel sheet and the material. The friction coefficient during lubricated rolling is preferably 0.10 or more. The friction coefficient during lubricated rolling is preferably 0.25 or less.

[0101] (pickling process) The hot-rolled steel sheet produced as described above may be subjected to pickling. Pickling can remove oxides from the steel sheet surface, and therefore can be performed to ensure good chemical conversion treatability and plating quality in the final high-strength steel sheet product. Pickling may be performed once or multiple times.

[0102] (Cold rolling process) The hot-rolled pickled sheet or hot-rolled steel sheet obtained as described above is subjected to cold rolling as necessary. When cold rolling is performed, the pickled sheet may be subjected to cold rolling as it is after hot rolling, or may be subjected to cold rolling after heat treatment. Optionally, the cold-rolled steel sheet obtained after cold rolling may be subjected to pickling. The cold rolling is carried out by multi-pass rolling requiring two or more passes, such as tandem multi-stand rolling or reverse rolling.

[0103] If necessary, the cold rolling reduction ratio: 20% to 80% When cold rolling is performed, the reduction ratio (cumulative reduction ratio) of the cold rolling is not particularly limited, but is preferably 20% or more and 80% or less. If the reduction ratio of the cold rolling is less than 20%, the steel structure is likely to become coarse and non-uniform in the annealing process, and there is a risk of the TS and bendability of the final product decreasing. Therefore, the reduction ratio of the cold rolling is preferably 20% or more. On the other hand, if the reduction ratio of the cold rolling exceeds 80%, the shape of the steel sheet is likely to be defective, and the amount of zinc coating may become non-uniform. Therefore, the reduction ratio of the cold rolling is preferably 80% or less.

[0104] (Metal plating (metal electroplating, first plating) process) In one embodiment of the present invention, a first plating step may be included in which metal plating is applied to one or both sides of the steel sheet after the hot rolling step (after the cold rolling step if cold rolling is performed) and before the annealing step to form a metal plating layer (first plating layer). For example, the surface of the hot-rolled steel sheet or cold-rolled steel sheet obtained as described above may be subjected to a metal electroplating treatment to obtain a pre-annealed metal electroplated steel sheet having a pre-annealed metal electroplating layer formed on at least one surface thereof. Note that the metal plating referred to here does not include zinc plating (second plating). The metal electroplating method is not particularly limited, but as described above, it is preferable to form a metal electroplating layer on the base steel sheet, and therefore it is preferable to carry out a metal electroplating process. For example, in the case of an Fe-based electroplating bath, a sulfuric acid bath, a hydrochloric acid bath, or a mixture of both can be used. The coating weight of the metal electroplating layer before annealing can be adjusted by the current application time, etc. Note that the metal electroplated steel sheet before annealing means that the metal electroplating layer has not been subjected to an annealing process, and does not exclude forms in which a hot-rolled steel sheet before metal electroplating, a pickled sheet after hot rolling, or a cold-rolled steel sheet has been annealed in advance.

[0105] Here, the metal species of the electroplating layer are Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Pt The metal may be any of Au, Hg, Ti, Pb, and Bi, but Fe is more preferable. In the following, Fe-based electroplating is used as an example, but the following conditions for Fe-based electroplating can be similarly adopted for other metal-based electroplating.

[0106] The Fe ion content in the Fe-based electroplating bath before the start of current application is 2+ The content of Fe ions in the Fe-based electroplating bath is preferably 0.5 mol / L or more. 2+ A sufficient amount of Fe can be obtained if the Fe ion content in the Fe-based electroplating bath before the start of current application is 0.5 mol / L or more. In order to obtain a sufficient amount of Fe, the Fe ion content in the Fe-based electroplating bath before the start of current application is preferably 2.0 mol / L or less.

[0107] The Fe-based electroplating bath may contain Fe ions and at least one element selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V, and Co. The total content of these elements in the Fe-based electroplating bath is preferably 10 mass% or less in the Fe-based electroplated layer before annealing. Metal elements may be contained as metal ions, and nonmetal elements may be contained as part of boric acid, phosphoric acid, nitric acid, organic acid, etc. The iron sulfate plating solution may also contain a conductivity aid such as sodium sulfate or potassium sulfate, a chelating agent, or a pH buffer.

[0108] Other conditions for the Fe-based electroplating bath are not particularly limited. The temperature of the Fe-based electroplating solution is preferably 30°C or higher, and preferably 85°C or lower, in consideration of the ability to maintain a constant temperature. The pH of the Fe-based electroplating bath is not particularly specified, but is preferably 1.0 or higher in order to prevent a decrease in current efficiency due to hydrogen generation, and is preferably 3.0 or lower in consideration of the electrical conductivity of the Fe-based electroplating bath. The current density is 10 A / dm from the viewpoint of productivity. 2 From the viewpoint of easily controlling the deposition weight of the Fe-based electroplating layer, it is preferable to set the current to 150 A / dm or more. 2 The sheet threading speed is preferably 5 mpm or more from the viewpoint of productivity, and is preferably 150 mpm or less from the viewpoint of stably controlling the amount of adhesion.

[0109] As a treatment before the Fe-based electroplating treatment, a degreasing treatment and water washing for cleaning the steel sheet surface, and further, a pickling treatment and water washing for activating the steel sheet surface can be performed. Following these pretreatments, the Fe-based electroplating treatment is performed. The method of the degreasing treatment and water washing is not particularly limited, and a normal method can be used. In the pickling treatment, various acids such as sulfuric acid, hydrochloric acid, nitric acid, and mixtures thereof can be used. Among them, sulfuric acid, hydrochloric acid, or mixtures thereof are preferable. The concentration of the acid is not particularly specified, but considering the ability to remove the oxide film and the prevention of roughness (surface defects) due to excessive pickling, 1 to 20 mass% is preferable. In addition, the pickling treatment solution may contain an antifoaming agent, a pickling promoter, a pickling inhibitor, etc.

[0110] (Annealing process) In one embodiment of the present invention, after the hot rolling step (after the cold rolling step if cold rolling is performed, after the metal plating step if metal plating to form a metal plating layer (first plating layer) is performed, and after the metal plating step if cold rolling and metal plating are performed), an annealing step is included in which the steel sheet is annealed under conditions of an annealing temperature of (Ac1+(Ac3-Ac1)×5 / 8)°C or higher and 950°C or lower, and a holding time of 20 seconds or longer.

[0111] Annealing temperature: (Ac1+(Ac3-Ac1)×5 / 8)℃ or higher and 950℃ or lower If the annealing temperature is less than (Ac1+(Ac3-Ac1)×5 / 8)°C, the ratio of austenite generated during heating in the two-phase region of ferrite and austenite becomes insufficient, and the area ratio of ferrite increases excessively after annealing, making it impossible to obtain the desired TS, YS, and YR. On the other hand, when the annealing temperature exceeds 950°C, the grain size of austenite becomes coarse, and finally, the average grain size of isolated islands of fresh martensite and isolated islands of retained austenite in the bainite grains and tempered bainite grains exceeds 2.00 μm, making it difficult to obtain good λ, R / t, ST and SFmax. Therefore, the annealing temperature is set to be equal to or higher than (Ac1+(Ac3-Ac1)×5 / 8)° C. and equal to or lower than 950° C. The annealing temperature is preferably equal to or lower than 900° C. Note that the annealing temperature is the maximum temperature reached in the annealing process.

[0112] The Ac1 point (℃) and Ac3 point (℃) can be calculated using the following formula. Ac1 point (℃)=727.0-32.7×[%C]+14.9×[%Si]+2.0×[%Mn] Ac3 point (℃)=912.0-230×[%C]+31.6×[%Si]-20.4×[%Mn] Here, [%C] is the C content (% by mass), [%Si] is the Si content (% by mass), and [%Mn] is the Mn content (% by mass).

[0113] Annealing time: 20 seconds or more If the annealing time is less than 20 seconds, the rate of austenite generation during heating in the two-phase region of ferrite and austenite becomes insufficient. Therefore, the area ratio of ferrite increases excessively after annealing, and TS, YS and YR cannot be obtained. Therefore, the annealing time is set to 20 seconds or more. The annealing time is preferably 30 seconds or more, and more preferably 50 seconds or more. Although the upper limit of the annealing time is not particularly limited, the annealing time is preferably 900 seconds or less, more preferably 800 seconds or less, further preferably 300 seconds or less, and further more preferably 220 seconds or less. The annealing time is the holding time in the temperature range of (annealing temperature -40°C) or more and (annealing temperature) or less. In other words, the annealing time includes not only the holding time at the annealing temperature, but also the residence time in the temperature range of (annealing temperature -40°C) or more and (annealing temperature) or less during heating and cooling before and after reaching the annealing temperature. The number of annealing steps may be two or more, but is preferably one from the viewpoint of energy efficiency.

[0114] Dew point of the annealing process atmosphere (annealing atmosphere): -30℃ or higher In one embodiment of the present invention, the dew point of the atmosphere in the annealing step (annealing atmosphere) is preferably -30°C or higher. By performing annealing in the annealing step with a dew point of -30°C or higher, the decarburization reaction is promoted and the surface soft layer can be formed deeper. The dew point of the annealing atmosphere in the annealing step is more preferably -25°C or higher, even more preferably above -20°C, even more preferably -15°C or higher, and most preferably -5°C or higher. Although there is no particular upper limit for the dew point of the annealing atmosphere in the annealing step, in order to suitably prevent oxidation of the surface of the Fe-based electroplating layer and to improve plating adhesion when a zinc plating layer is formed, the dew point of the annealing atmosphere in the annealing step is preferably 30° C. or less, more preferably 25° C. or less, and even more preferably 20° C. or less.

[0115] (First cooling process) In the present invention, after the annealing step, a first cooling step of cooling to a first cooling stop temperature of 300° C. or more and 550° C. or less is included.

[0116] First cooling stop temperature: 300℃ or more and 550℃ or less If the first cooling stop temperature is less than 300° C. or more than 550° C., the area fraction of bainite and tempered bainite will be 10.0% or less, making it difficult to ensure good ductility, that is, to obtain a desired El. In addition, the average crystal grain size of the isolated islands of fresh martensite and isolated islands of retained austenite in the bainite grains and tempered bainite grains exceeds 2.00 μm. Furthermore, the average crystal grain size of the carbides in the bainite grains and tempered bainite grains exceeds 500 nm, and the number density of the carbides in the bainite grains and tempered bainite grains with a grain size of 300 nm or more is 3.0 pieces / μm. 2 In some cases, the temperature exceeds 300° C. This makes it difficult to obtain good λ, R / t, ST, and SFmax. Therefore, in the present invention, after the annealing step, the first cooling stop temperature is set to 300° C. or more and 550° C. or less, and the steel is cooled to this first cooling stop temperature.

[0117] (Intermediate holding process) Intermediate holding temperature: 300℃ to 550℃, intermediate holding time: 20 seconds or more In the present invention, after the first cooling step, the intermediate holding step is performed under the conditions of an intermediate holding temperature of 300° C. or more and 550° C. or less and a holding time of 20 seconds or more. If the intermediate holding temperature is less than 300°C or exceeds 550°C, or if the holding time (intermediate holding time) is 20 seconds or longer, the area ratio of bainite and tempered bainite will be 10.0% or less, making it difficult to ensure good ductility, i.e., to obtain the desired El. In addition, the average crystal grain size of isolated islands of fresh martensite and isolated islands of retained austenite within the bainite grains and tempered bainite grains will exceed 2.00 μm. Furthermore, the average crystal grain size of carbides within the bainite grains and tempered bainite grains will exceed 500 nm, and the number density of carbides with a grain size of 300 nm or more within the bainite grains and tempered bainite grains will be 3.0 / μm. 2 This makes it difficult to obtain good λ, R / t, ST and SFmax. Therefore, in the present invention, in the intermediate holding step, holding is performed under the conditions of an intermediate holding temperature of 300° C. or more and 550° C. or less and a holding time (intermediate holding time) of 20 seconds or more.

[0118] (Zinc plating process (second plating process)) In the present invention, after the intermediate holding step, the steel sheet may be subjected to a zinc plating treatment. By performing the zinc plating treatment, a zinc-plated steel sheet can be obtained. Examples of the galvanizing treatment include hot-dip galvanizing treatment and galvannealing treatment.

[0119] In the case of hot-dip galvanizing, it is preferable to immerse the steel sheet in a galvanizing bath at 440°C to 500°C, and then adjust the coating weight by gas wiping or the like. The hot-dip galvanizing bath is not particularly limited as long as it has the composition of the galvanized layer described above, but it is preferable to use a plating bath with an Al content of 0.10 mass% or more, with the balance being Zn and unavoidable impurities. The Al content is preferably 0.23 mass% or less.

[0120] In the case of galvannealing treatment, it is preferable to carry out alloying treatment by heating the hot-dip galvanized steel sheet to an alloying temperature of 450° C. or higher after carrying out the hot-dip galvanizing treatment as described above. The above alloying temperature is preferably 600° C. or lower. If the alloying temperature is less than 450°C, the Zn-Fe alloying rate is slow, and alloying may be difficult. On the other hand, if the alloying temperature exceeds 600°C, untransformed austenite is transformed into pearlite, and it is difficult to achieve a TS of 1180MPa or more. The alloying temperature is more preferably 500°C or more, and further preferably 510°C or more. The alloying temperature is more preferably 570°C or less.

[0121] In addition, the coating weight of both hot-dip galvanized steel sheet (GI) and galvannealed steel sheet (GA) is 20 g / m per side. 2The coating weight of the zinc-plated layer on one side is preferably 80 g / m or more. 2 It is preferable that the plating thickness is set to be equal to or less than 100 nm. The plating thickness can be adjusted by gas wiping or the like.

[0122] (Second cooling process) In the present invention, after the intermediate holding step (after the zinc plating step if a zinc plating step is used), the steel sheet is subjected to a pressure of 2.0 kgf / mm in a temperature range of 300°C to 450°C. 2 The steel sheet is subjected to at least five passes of tension while being in contact with a roll having a diameter of 500 mm or more and 1,500 mm or less for one quarter of the circumference of the roll per pass, and then cooled to a cooling stop temperature (second cooling stop temperature) of less than 300°C.

[0123] Tension applied in the temperature range of 300℃ to 450℃: 2.0kgf / mm 2 End In the present invention, as described above, the steel plate is subjected to a stress of 2.0 kgf / mm 2 By applying the above tension at least once, most of the austenite becomes martensite through processing (stress / strain) induced transformation, and is then tempered in the reheating process, reducing the area ratio of fresh martensite in the final structure and ensuring an appropriate amount of tempered martensite. In addition, the amount of austenite immediately after the second cooling process can be reduced, reducing the volume ratio of retained austenite in the final structure. As a result, the desired λ, R / t, ST, and SFmax can be obtained. Here, the tension is calculated by multiplying the total load (kgf) of the load cells on the left and right sides of the roll by the cross-sectional area of ​​the steel plate (= plate thickness (mm) × plate width (mm)) (mm 2 The load cell must be placed parallel to the tension direction. The load cells are preferably disposed 200 mm from both ends of the roll. The length of the roll used is preferably 1500 mm or more. The length of the roll used is preferably 2500 mm or less. The tension is preferably 2.2 kgf / mm 2More preferably, it is 2.4 kgf / mm 2 The tension is preferably 15.0 kgf / mm 2 More preferably, it is 10.0 kgf / mm 2 This tension is more preferably 7.0 kgf / mm 2 and even more preferably 4.0 kgf / mm 2 The following is the result.

[0124] The steel sheet is passed through rolls with diameters of 500 mm to 1500 mm for 1 / 4 of the roll circumference per pass. Number of passes: 5 or more In the present invention, the steel sheet is passed through 5 or more passes of rolls having a diameter of 500 mm to 1500 mm, with the roll contacting the steel sheet for 1 / 4 rotation per pass. This causes most of the austenite to become martensite by processing (stress / strain) induced transformation, and then the steel sheet is tempered in the reheating process, so that the area ratio of fresh martensite in the final structure can be reduced and an appropriate amount of tempered martensite can be secured. In addition, the amount of austenite immediately after the second cooling process can be reduced, and the volume ratio of retained austenite in the final structure can be reduced. As a result, the desired λ, R / t, ST and SFmax can be obtained. The number of passes is preferably 6 or more, and more preferably 7 or more. Although there is no particular upper limit, the number of passes is preferably 10 passes or less, and more preferably 9 passes or less.

[0125] Second cooling stop temperature: less than 300℃ The cooling conditions of the second cooling step are not particularly limited, and may be in accordance with a conventional method. For example, gas jet cooling, mist cooling, roll cooling, water cooling, and air cooling can be applied as the cooling method. By setting the second cooling stop temperature to less than 300°C, an appropriate amount of austenite is transformed into martensite, and then tempered in the reheating step, so that the area ratio of fresh martensite in the final structure can be reduced, and further, an appropriate amount of tempered martensite can be secured. In addition, the amount of austenite immediately after the second cooling step can be reduced, and the volume ratio of retained austenite in the final structure can be reduced. As a result, desired λ, R / t, ST, and SFmax can be obtained. From the viewpoint of preventing oxidation of the surface, it is preferable to cool to 250°C or less. Although the lower limit is not particularly limited, it is preferable to set it to room temperature (-5°C or more and 55°C or less). For example, the average cooling rate is preferably 1°C / second or more. In addition, the average cooling rate is preferably 50°C / second or less. Here, the average cooling rate (°C / s) is calculated by (cooling start temperature (°C)-cooling stop temperature (°C)) / cooling time (s).

[0126] (Reheating process) After the second cooling step, in the reheating step, the steel sheet is reheated to a temperature range of not less than the cooling stop temperature (second cooling stop temperature) and not more than 440° C., and held for not less than 20 seconds.

[0127] Reheating temperature: Temperature range from the above cooling stop temperature (second cooling stop temperature) to 440°C Reheating holding time: 20 seconds or more In the present invention, by reheating to the cooling stop temperature (second cooling stop temperature) or higher and holding for 20 seconds or more, diffusible hydrogen in the steel is released. In addition, the area ratio of fresh martensite in the final structure can be reduced, and an appropriate amount of tempered martensite can be secured. In addition, the amount of austenite immediately after the second cooling process can be reduced, and the volume ratio of retained austenite in the final structure can be reduced. As a result, desired λ, R / t, ST, and SFmax can be obtained. On the other hand, if the reheating temperature exceeds 440°C, when zinc plating is performed, the zinc plating partly dissolves and adheres to the roll, and a uniformly zinc-plated hot-dip galvanized steel sheet cannot be obtained. Also, if the reheating holding time is less than 20 seconds, the desired amount of diffusible hydrogen in the steel is not released. Therefore, in the present invention, the material is reheated to a temperature range of not less than the second cooling stop temperature and not more than 440° C., and held at that temperature for not less than 20 seconds. The reheating temperature is preferably 40°C or higher, more preferably 160°C or higher. The reheating temperature is preferably 420° C. or lower, and more preferably 320° C. or lower. The reheating holding time is preferably 25 seconds or more, and more preferably 30 seconds or more. The reheating holding time is preferably 300 seconds or less, and more preferably 200 seconds or less.

[0128] The steel sheet obtained as described above may be further subjected to temper rolling. If the reduction rate of temper rolling exceeds 2.00%, the yield stress increases, and the dimensional accuracy may decrease when the steel sheet is formed into a member. Therefore, the reduction rate of temper rolling is preferably 2.00% or less. The lower limit of the reduction rate of temper rolling is not particularly limited, but is preferably 0.05% or more from the viewpoint of productivity. The temper rolling may be performed on an apparatus continuous with the annealing apparatus for performing each of the above-mentioned steps (online), or may be performed on an apparatus discontinuous with the annealing apparatus for performing each of the steps (offline). The number of rolling times of temper rolling may be one or two or more. As long as the same elongation rate as that of temper rolling can be imparted, rolling using a leveler or the like may be used.

[0129] Other manufacturing method conditions are not particularly limited, but from the viewpoint of productivity, it is preferable to carry out a series of processes such as the above-mentioned annealing, hot-dip galvanizing, and alloying treatment of galvanizing in a CGL (Continuous Galvanizing Line), which is a hot-dip galvanizing line. After hot-dip galvanizing, wiping is possible to adjust the coating weight. Note that the plating conditions other than the above-mentioned conditions can be based on the usual hot-dip galvanizing method.

[0130] [3. Materials] Next, a member according to one embodiment of the present invention will be described. A member according to one embodiment of the present invention is a member made using the above-mentioned steel plate (as a raw material). For example, the raw material steel plate is subjected to at least one of forming and joining to form a member. Here, the above steel plate has a TS of 1180 MPa or more, high YS and YR, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance properties during collision (bending fracture properties and axial crush properties). Therefore, the member according to one embodiment of the present invention has high strength and excellent impact resistance properties. Therefore, the member according to one embodiment of the present invention is particularly suitable for application to impact energy absorbing members used in the automotive field.

[0131] [4. Manufacturing methods for components] Next, a method for manufacturing a member according to one embodiment of the present invention will be described. A method for manufacturing a component according to one embodiment of the present invention includes a step of subjecting the above-mentioned steel plate (e.g., a steel plate manufactured by the above-mentioned steel plate manufacturing method) to at least one of forming and joining to form a component. Here, the molding method is not particularly limited, and for example, a general processing method such as press processing can be used. The joining method is also not particularly limited, and for example, general welding such as spot welding, laser welding, and arc welding, rivet joining, crimp joining, etc. The molding conditions and joining conditions are not particularly limited, and may be in accordance with ordinary methods. EXAMPLES

[0132] Steel materials having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) were melted in a converter and made into steel slabs by a continuous casting method. In Table 1, "-" indicates the content of unavoidable impurities. The calculated transformation points Ac1 (°C) and Ac3 (°C) shown in Table 1 were calculated using the following formula. Ac1 point (℃)=727.0-32.7×[%C]+14.9×[%Si]+2.0×[%Mn] Ac3 point (℃)=912.0-230×[%C]+31.6×[%Si]-20.4×[%Mn] Here, [%C] is the C content, [%Si] is the Si content, and [%Mn] is the Mn content.

[0133] The obtained steel slab was heated to 1200°C, and after heating, the steel slab was subjected to rough rolling and hot rolling to obtain hot-rolled steel sheets. Next, Nos. 1 to 56, 60 to 83, 92 to 106, and 112 to 117 of the obtained hot-rolled steel sheets were pickled and cold rolled to obtain cold-rolled steel sheets having the thicknesses shown in Tables 3, 5, and 7. In addition, Nos. 57 to 59, 84 to 91, and 107 to 111 of the obtained hot-rolled steel sheets were pickled to obtain hot-rolled steel sheets (white skin) having the thicknesses shown in Tables 3, 5, and 7. Next, the obtained cold-rolled steel sheet or hot-rolled steel sheet (white skin) is subjected to treatments in an annealing step, a first cooling step, an intermediate holding step, a galvanizing step, a second cooling step, and a reheating step under the conditions shown in Table 2, In addition, under the conditions shown in Table 4, the first plating step (metal plating step), the annealing step, the first cooling step, the intermediate holding step, the second plating step (galvanizing step), the second cooling step and the reheating step were performed to obtain a steel sheet (galvanized steel sheet). Moreover, under the conditions shown in Table 6, the first plating step (metal plating step), the annealing step, the first cooling step, the intermediate holding step, the second cooling step and the reheating step were performed to obtain steel sheets.

[0134] Here, in the galvanizing process, a hot-dip galvanizing treatment or a galvannealed treatment was performed to obtain a hot-dip galvanized steel sheet (hereinafter also referred to as GI) or an alloyed hot-dip galvanized steel sheet (hereinafter also referred to as GA). In Table 2, the type of plating process is also indicated as "GI" or "GA". In Tables 2 and 4, the alloying temperature is indicated as - because no alloying treatment is performed in the case of GI steel sheets. In Table 6, no galvanizing treatment is performed, and the steel sheets are indicated as CR (cold-rolled steel sheet (uncoated)) or HR (hot-rolled steel sheet (uncoated)).

[0135] The galvanizing bath temperature was 470°C for both GI and GA production. When manufacturing GI, the amount of zinc plating is 45 to 72 g / m per side. 2 When manufacturing GA, the thickness is 45 g / m per side. 2 It was decided. The composition of the zinc coating layer of the finally obtained hot-dip galvanized steel sheet was as follows: GI: 0.1-1.0 mass% Fe, 0.2-0.33 mass% Al, and the balance was Zn and unavoidable impurities, while GA: 8.0-12.0 mass% Fe, 0.1-0.23 mass% Al, and the balance was Zn and unavoidable impurities. In addition, the zinc plating layers were formed on both sides of the base steel sheet in each case.

[0136] The steel structure of the base steel sheet was identified using the obtained steel sheet in the manner described above. The measurement results are shown in Tables 3, 5, and 7. In Tables 3, 5, and 7, F is ferrite, M is martensite, RA is retained austenite, B and BT are bainite and tempered bainite, TM is tempered martensite, P is pearlite, θ is carbide, and F' is unrecrystallized ferrite.

[0137] The method for measuring the surface soft layer is as follows. After smoothing the thickness cross section (L cross section) parallel to the rolling direction of the steel plate by wet polishing, measurements were taken at 1 μm intervals from a position 1 μm from the steel plate surface in the thickness direction to a position 100 μm in the thickness direction using a Vickers hardness tester based on JIS Z 2244-1 (2020) with a load of 10 gf. Measurements were then taken at 20 μm intervals up to the center of the plate thickness. The region where the hardness has decreased to 85% or less compared to the hardness at the 1 / 4 position of the plate thickness is defined as the soft layer (surface soft layer), and the thickness in the thickness direction of the region is defined as the thickness of the soft layer.

[0138] In Tables 1 to 7, the underlined portions indicate values ​​outside the appropriate range of the present invention. In addition, tensile tests, hole expansion tests, V-bend tests, U-bend + contact bending tests, V-bend + orthogonal VDA bending tests, and axial crush tests were performed according to the following procedures, and the tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limit hole expansion ratio (λ), R / t in the V-bend test, limit spacer thickness (ST) in the U-bend + contact bending test, stroke at maximum load (SFmax) measured in the V-bend + orthogonal VDA bending test, and the presence or absence of fracture (visual cracks) in the axial crush test were evaluated according to the following criteria.

[0139] ·TS 〇(Pass): 1180MPa or more × (Fail): Less than 1180MPa

[0140] YS 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 750MPa≦YS (B) When TS is 1320MPa or less, YS is 850MPa or less ×(Fail): (A) When 1180MPa≦TS<1320MPa, 750MPa>YS (B) When 1320MPa≦TS, 850MPa>YS

[0141] ·YR 〇(Pass): 0.64≦YR ×(Fail):0.64>YR

[0142] ·El 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 8.0%≦El (B) 1320MPa≦TS, 7.0%≦El ×(Fail): (A) When 1180MPa≦TS<1320MPa, 8.0%>El (B) When 1320MPa≦TS, 7.0%>El

[0143] λ 〇(Pass): 25% or more × (Fail): Less than 25%

[0144] R / t 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 2.5≧R / t (B) When TS is 1320MPa or less, R / t is 3.0 or more ×(Fail): (A) 2.5 when 1180MPa≦TS<1320MPa <R / t (B) 3.0 when 1320MPa ≤ TS <R / t

[0145] ·ST 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 5.5mm≧ST (B) When TS is 1320MPa or less, ST is 6.0mm or more ×(Fail): (A) 5.5 mm when 1180 MPa ≤ TS < 1320 MPa <ST (B) 6.0 mm when TS is 1320 MPa or less <ST

[0146] ·SFmax 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 25.5mm≦SFmax (B)1320MPa≦TS, 24.5mm≦SFmax ×(Fail): (A) When 1180MPa≦TS<1320MPa, 25.5mm>SFmax (B) When 1320MPa≦TS, 24.5mm>SFmax

[0147] - Presence or absence of axial crushing fracture (exterior cracks) ⊚ (Pass): No visible cracks were observed in the sample after the axial crush test. 〇 (Pass): One or less external cracks were observed on the sample after the axial crush test. × (Fail): Two or more external cracks were observed on the sample after the axial crush test.

[0148] (1) Tensile test The tensile test was performed in accordance with JIS Z 2241 (2011). That is, JIS No. 5 test pieces were taken from the obtained steel sheets so that the longitudinal direction was perpendicular to the rolling direction of the base steel sheet. Using the taken test pieces, tensile tests were performed at a crosshead speed of 10 mm / min, and TS, YS, YR and El were measured. The results are shown in Tables 3, 5 and 7.

[0149] (2) Hole expansion test The hole expansion test was performed in accordance with JIS Z 2256 (2020). That is, a test piece of 100 mm × 100 mm was taken from the obtained steel plate by shear processing. A hole of 10 mm in diameter was punched in the test piece with a clearance of 12.5%. Next, a wrinkle holding force of 9 ton (88.26 kN) was applied around the hole using a die with an inner diameter of 75 mm, and a conical punch with an apex angle of 60 ° was pressed into the hole, and the diameter of the hole of the test piece at the crack occurrence limit (when cracks occurred) was measured. Then, the limit hole expansion ratio: λ (%) was calculated by the following formula. In addition, λ is an index for evaluating the stretch flangeability. The results are shown in Tables 3, 5, and 7. λ(%)={(D f -D0) / D0}×100 Where: D f : diameter of the hole in the test piece when the crack occurred (mm) D0: Initial diameter of the hole in the test piece (mm) It is.

[0150] (3) V-bend test The V (90°) bending test was performed in accordance with JIS Z 2248 (2014). A test piece of 100 mm × 35 mm was taken from the obtained steel plate by shearing and end face grinding, where the 100 mm side was parallel to the width (C) direction. Bending radius R: Varies in 0.5mm increments Test method: Die support, punch push Molding load: 10ton Test speed: 30mm / min Holding time: 5s Bending direction: perpendicular to rolling (C) direction The evaluation was carried out three times, and R / t was calculated by dividing the minimum bending radius (critical bending radius) R at which cracks did not appear by the plate thickness t. In addition, using a Leica stereo microscope, cracks with a length of 200 μm or more at 25x magnification were judged to be cracks. R / t is an index for evaluating the bendability of press formability. The results are shown in Tables 3, 5, and 7.

[0151] (4) U-bend + close bend test The U-bend + close bending test was carried out as follows. From the obtained steel plate, a 60 mm × 30 mm test piece was taken by shearing and edge grinding. Here, the 60 mm side is parallel to the width (C) direction. The test piece was prepared by U-bending (primary bending) in the width (C) direction with the rolling (L) direction as the axis with a curvature radius / plate thickness of 4.2. In the U-bending (primary bending), as shown in FIG. 2(a), a punch B1 was pressed into the steel plate placed on the roll A1 to obtain a test piece T1. Next, as shown in FIG. 2(b), the test piece T1 placed on the lower die A2 was subjected to close bending (secondary bending) in which it was crushed by the upper die B2. In FIG. 2(a), D1 indicates the width (C) direction and D2 indicates the rolling (L) direction. Note that a spacer S, which will be described later, was inserted between the test pieces.

[0152] The U-bending conditions in the U-bending + close bending test are as follows. Test method: Roll support, punch intrusion Punch tip R: 5.0mm Roll and punch clearance: Sheet thickness + 0.1 mm Stroke speed: 10mm / min Bending direction: perpendicular to rolling (C) direction The conditions for the U-bend + close bending test are as follows: Spacer thickness: Varies in 0.5mm increments Test method: Die support, punch push Molding load: 10ton Test speed: 10mm / min Holding time: 5s Bending direction: perpendicular to rolling (C) direction

[0153] The above U-bend + close bending test was performed three times, and the limit spacer thickness (ST) was determined when no cracks occurred in all three tests. In addition, using a Leica stereo microscope, cracks with a length of 200 μm or more at 25x magnification were determined to be cracks. ST is an index for evaluating the fracture resistance properties during a collision (the fracture resistance properties of the vertical wall in an axial crushing test). The results are shown in Tables 3, 5, and 7.

[0154] (5) V-bend + orthogonal VDA bend test The V-bend + orthogonal VDA bend test is carried out as follows. From the obtained steel plate, a 60 mm × 65 mm test piece was taken by shearing and edge grinding. Here, the 60 mm side is parallel to the rolling (L) direction. The test piece was prepared by bending the steel plate 90° (primary bending) in the rolling (L) direction with the width (C) direction as the axis at a curvature radius / plate thickness of 4.2. In the 90° bending (primary bending), as shown in Figure 3(a), a punch B3 was pressed into the steel plate placed on a die A3 with a V groove to obtain a test piece T1. Next, as shown in Figure 3(b), a punch B4 was pressed into the test piece T1 placed on a support roll A4 so that the bending direction was perpendicular to the rolling direction, and an orthogonal bending (secondary bending) was performed. In Figures 3(a) and 3(b), D1 indicates the width (C) direction, and D2 indicates the rolling (L) direction.

[0155] The V-bending conditions in the V-bending + orthogonal VDA bending test are as follows: Test method: Die support, punch push Molding load: 10ton Test speed: 30mm / min Holding time: 5s Bending direction: Rolling (L) direction

[0156] The VDA bending conditions in the V-bending + orthogonal VDA bending test are as follows: Test method: Roll support, punch intrusion Roll diameter: φ30mm Punch tip R: 0.4 mm Distance between rolls: (sheet thickness x 2) + 0.5 mm Stroke speed: 20mm / min Test piece size: 60mm x 60mm Bending direction: perpendicular to rolling (C) direction

[0157] The stroke at maximum load is determined from the stroke-load curve obtained when the VDA bending is performed. The average stroke at maximum load when the V bending + orthogonal VDA bending test is performed three times is taken as SFmax (mm). SFmax is an index for evaluating fracture resistance properties during a collision (fracture resistance properties of the bent ridgeline in an axial crushing test). The results are shown in Tables 3, 5, and 7.

[0158] (6) Axial crush test A 160 mm x 200 mm test piece was taken from the obtained steel plate by shearing. Here, the 160 mm side was parallel to the rolling (L) direction. Using a die with a punch shoulder radius of 5.0 mm and a die shoulder radius of 5.0 mm, the test piece was formed (bended) to a depth of 40 mm to produce the hat-shaped component 10 shown in Figures 4(a) and 4(b). The steel plate used as the material for the hat-shaped component was cut into 80 mm x 100 mm pieces. 200The test member 30 was cut out separately to a size of mm. Next, the cut-out steel plate 20 and the hat-shaped member 10 were spot-welded to prepare a test member 30 as shown in FIG. 4(a) and FIG. 4(b). FIG. 4(a) is a front view of the test member 30 prepared by spot-welding the hat-shaped member 10 and the steel plate 20. FIG. 4(b) is a perspective view of the test member 30. The position of the spot welded portion 40 was such that the end of the steel plate and the welded portion were spaced 10 mm apart, and the welded portions were spaced 45 mm apart, as shown in FIG. 4(b). Next, as shown in FIG. 4(c), the test member 30 was joined to the base plate 50 by TIG welding to prepare a sample for an axial crush test. Next, an impactor 60 was made to collide with the prepared sample for an axial crush test at a constant speed of 10 mm / min, and the sample for an axial crush test was crushed to 70 mm. 4(c), the crushing direction D3 was parallel to the longitudinal direction of the test member 30. The results are shown in Tables 3, 5 and 7.

[0159] Considering the effect of plate thickness, the U-bend + close bending test, V-bend + orthogonal VDA bending test, and axial crushing test were all conducted on steel plates with a thickness of 1.2 mm. Steel plates with a thickness of 1.2 mm or more were ground on one side to make the plate thickness 1.2 mm. Because grinding may affect the bendability of the steel plate surface, in the U-bend + close bending test, the ground surface was placed on the inside of the bend (valley side), and in the V-bend + orthogonal VDA bending test, the ground surface was placed on the outside of the bend (mountain side) during the V-bend test, and then the ground surface was placed on the inside of the bend (valley side) during the subsequent VDA bending test.On the other hand, in the U-bend + close bending test, V-bend + orthogonal VDA bending test, and axial crushing test of steel plates with a thickness of 1.2 mm or less, the effects of plate thickness are small, so the tests were performed without grinding.

[0160] <Nano hardness measurement> In order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, when the nanohardness is measured at 300 or more points in a 50μm×50μm region on the sheet surface at 1 / 4 and 1 / 2 positions in the sheet thickness direction from the surface layer of the base steel sheet, it is more preferable that the number of measurements of nanohardness of 7.0GPa or more at 1 / 4 positions in the sheet thickness direction from the surface of the soft surface layer is 0.10 or less relative to the total number of measurements at 1 / 4 positions in the sheet thickness direction. If the ratio of nanohardness of 7.0GPa or more is 0.10 or less, it means that the ratio of hard structures (martensite, etc.), inclusions, etc. is small, so it is possible to further suppress the generation and connection of voids and the development of cracks in hard structures (martensite, etc.) and inclusions during press forming and collision, and excellent R / t and SFmax are obtained.

[0161] In this example, when plating was applied, after peeling off the plating layer, the steel sheet was mechanically polished from the surface to a position 1 / 4 of the way down to the soft surface layer at -5 μm, and then buffed with diamond and alumina from the surface of the steel sheet to a position 1 / 4 of the way down to the soft surface layer at -5 μm, followed by colloidal silica polishing. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions.

[0162] Next, the surface soft layer was mechanically polished to a position halfway down the thickness direction, buffed with diamond and alumina, and polished with colloidal silica. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions.

[0163] [Table 1-1]

[0164]

Table 1-2

[0165]

Table 2-1

[0166]

Table 2-2

[0167]

Table 3-1

[0168]

Table 3-2

[0169]

Table 4

[0170]

Table 5-1

[0171]

Table 5-2

[0172]

Table 6

[0173]

Table 7-1

[0174] [Table 7-2]

[0175] As shown in Tables 3, 5, and 7, all of the examples of the invention passed the tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limiting hole expansion ratio (λ), R / t in the V-bend test, limiting spacer thickness (ST) in the U-bend + close contact bending test, and stroke at maximum load (SFmax) measured in the V-bend + orthogonal VDA bending test, and there was no fracture (visual cracking) in the axial crush test. On the other hand, in the comparative examples, at least one of the following was insufficient: tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limiting hole expansion ratio (λ), R / t in the V-bend test, limiting spacer thickness (ST) in the U-bend + tight-fitting bend test, stroke at maximum load (SFmax) measured in the V-bend + orthogonal VDA bend test, and the presence or absence of fracture (visual cracking) in the axial crush test. In Tables 5 and 7, when the dew point was in the range of -30°C or higher and -20°C or lower, the thickness of the soft surface layer was 14 μm or less, and the fracture (visual cracking) in the axial crushing test was judged to be "○". However, even when the thickness of the soft surface layer was 14 μm or less, if a metal plating layer was present, the fracture (visual cracking) in the axial crushing test was judged to be "◎".

[0176] In addition, the components obtained by forming or joining the steel plates of the present invention had excellent properties characteristic of the present invention in terms of tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limiting hole expansion ratio (λ), R / t in a V-bend test, limiting spacer thickness (ST) in a U-bend + close contact bending test, and stroke at maximum load (SFmax) measured in a V-bend + orthogonal VDA bending test, and there were no fractures (visual cracks) in an axial compression test, indicating that the components had the excellent properties characteristic of the present invention. [Explanation of symbols]

[0177] 10 Hat-shaped member 20 steel plate 30 Test components 40 Spot welds 50 Main plate 60 Impactor A1 Die A2 Support roll A3 Die A4 support roll B1 Punch B2 Punch B3 Punch B4 punch D1 width (C) direction D2 Rolling (L) direction D3 Crushing direction S Spacer T1 test piece F Ferrite M Martensite RA Retained austenite B Bainite BT Tempered Bainite TM Tempered martensite θ Carbide [Industrial Applicability]

[0178] According to the present invention, it is possible to manufacture steel plates and members having a TS of 1180 MPa or more, high YS and YR, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance properties during collision (bending fracture properties and axial crush properties). Furthermore, by applying the steel plates and members obtained according to the method of the present invention to, for example, automobile structural members, it is possible to improve fuel efficiency by reducing the weight of the vehicle body, and the industrial value of the steel plates and members is extremely great.

Claims

1. A steel plate comprising a base steel plate, the base steel plate comprising: In mass percent, C: 0.030% or more and 0.250% or less, Si: 0.01% or more and 0.75% or less, Mn: 2.00% or more and less than 3.50%; P: 0.001% or more and 0.100% or less, S: 0.0200% or less, Al: 0.010% or more and 2.000% or less, N: 0.0100% or less, and the balance being Fe and unavoidable impurities; The structure at 1 / 4 of the sheet thickness of the base steel sheet is as follows: Ferrite area ratio: less than 20.0%; Area ratio of fresh martensite: 15.0% or less, Area ratio of retained austenite: 3.0% or less, Area ratio of bainite and tempered bainite: more than 10.0% and not more than 70.0%; Area ratio of tempered martensite: 30.0% or more and 80.0% or less, Area ratio of remaining structures other than ferrite, fresh martensite, retained austenite, bainite, tempered bainite, and tempered martensite: 10.0% or less; Furthermore, the average grain size of island-shaped fresh martensite and island-shaped retained austenite in the bainite grains and tempered bainite grains is 2.00 μm or less, The average grain size of carbides in bainite grains and tempered bainite grains is 500 nm or less; Furthermore, the number density of carbides having a grain size of 300 nm or more in the bainite grains and the tempered bainite grains is 3.0 particles / μm 2 A steel structure having the following structure: having The steel sheet has a diffusible hydrogen content of 0.50 mass ppm or less and a tensile strength of 1,180 MPa or more.

2. The composition further includes, in mass%, Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less; REM: 0.0200% or less The steel sheet according to claim 1, further comprising at least one element selected from the group consisting of:

3. The steel plate according to claim 1, which satisfies one or more of the following (A), (B) and (C): (A) The steel sheet has a zinc-plated layer as the outermost layer on one or both sides. (B) When the base steel sheet has a surface layer in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction, The surface layer has a surface soft layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 or more points in a 50 μm×50 μm region on the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, the ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet to the total number of measurements at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer is 0.10 or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position of ¼ of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less. (C) The steel sheet has a metal plating layer (excluding the zinc plating layer) formed on one or both sides of the base steel sheet.

4. The steel plate according to claim 2, which satisfies one or more of the following (A), (B) and (C): (A) The steel sheet has a zinc-plated layer as the outermost layer on one or both sides. (B) When the base steel sheet has a surface layer in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction, The surface layer has a surface soft layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 or more points in a 50 μm×50 μm region on the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, the ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet to the total number of measurements at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer is 0.10 or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position of ¼ of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less. (C) The steel sheet has a metal plating layer (excluding the zinc plating layer) formed on one or both sides of the base steel sheet.

5. A member made using the steel plate according to any one of claims 1 to 4.

6. A steel slab having the composition according to claim 1 or 2, A hot rolling process in which hot rolling is performed under a finish rolling temperature of 820°C or higher to obtain a hot-rolled steel sheet; The steel sheet after the hot rolling process is subjected to annealing at a temperature of: (Ac 1 + (Ac 3 -Ac 1 ) × 5 / 8) ° C. or higher and 950 ° C. or lower, and annealing time: 20 seconds or more; and After the annealing step, a first cooling step is performed to cool the steel sheet to a temperature range of 300° C. or more and 550° C. or less. After the first cooling step, an intermediate holding step is performed under the conditions of an intermediate holding temperature of 300° C. or more and 550° C. or less and a holding time of 20 seconds or more. The steel sheet after the intermediate holding step is subjected to a pressure of 2.0 kgf / mm in a temperature range of 300°C to 450°C. 2 Applying a tension of more than Thereafter, the steel sheet is passed through five or more passes while being in contact with a roll having a diameter of 500 mm or more and 1500 mm or less for one pass for a quarter of a rotation of the roll, Then, a second cooling step of cooling to a cooling stop temperature of less than 300°C; A reheating step of reheating the steel sheet to a temperature range of the cooling stop temperature or higher and 440°C or lower after the second cooling step and holding the temperature for 20 seconds or more, Alternatively, the present invention further comprises a base steel sheet satisfying one or more selected from the following (a), (b) and (c), wherein the structure at a 1 / 4 position of the sheet thickness of the base steel sheet has an area ratio of ferrite: less than 20.0%, an area ratio of fresh martensite: 15.0% or less, an area ratio of retained austenite: 3.0% or less, an area ratio of bainite and tempered bainite: more than 10.0% and 70.0% or less, and an area ratio of tempered martensite: 30.0% or more and 80.0% or less, the area ratio of residual structures other than ferrite, fresh martensite, retained austenite, bainite, tempered bainite, and tempered martensite is 10.0% or less, the average crystal grain size of island-shaped fresh martensite and island-shaped retained austenite in bainite grains and tempered bainite grains is 2.00 μm or less, the average crystal grain size of carbides in bainite grains and tempered bainite grains is 500 nm or less, and the number density of carbides having a grain size of 300 nm or more in bainite grains and tempered bainite grains is 3.0 pieces / μm 2 or less, The method for producing a steel sheet, wherein the base steel sheet contains a diffusible hydrogen amount of 0.50 ppm by mass or less and has a tensile strength of 1,180 MPa or more. (a) A cold rolling step is included in which the steel sheet after the hot rolling step and before the annealing step is subjected to cold rolling at a rolling reduction rate of 20% or more and 80% or less to obtain a cold-rolled steel sheet. (b) a galvanizing step of subjecting the steel sheet after the intermediate holding step and before the second cooling step to a galvanizing treatment to form a galvanized layer on the steel sheet. (c) A metal plating step is included in which, after the hot rolling step and before the annealing step, metal plating is applied to one or both sides of the steel sheet to form a metal plating layer.

7. The method for producing a steel sheet according to claim 6, wherein the annealing in the annealing step is performed in an atmosphere with a dew point of -30°C or higher.

8. A method for manufacturing a component, comprising a step of subjecting the steel plate according to any one of claims 1 to 4 to at least one of forming and joining to form a component.

Citation Information

Patent Citations

  • Preparation of instant porridge from hulled buckwheat seed

    JP1981099764A

  • Rust preventive painting method of automotive body

    JP1984053693A

  • Reeling method for thread

    JP1985052472A

  • High strength steel and manufacturing method

    JP2017507241A

  • High-strength steel sheet, high-strength hot-dip galvanized steel sheet, and high-strength hot-dip galvannealed steel sheet with excellent stretch flangeability and collision resistance, and method for producing the same

    JP3887235B2